Deep Phylogenomic Structure and Microendemism in Baja California Ammotrechidae (Arachnida: Solifugae) Support a Model of Distributed Diversification - Matthew R. Graham; Carlos E. Santibáñez‐López; R. Ryan Jones; Joshua A. Idjadi; Athenea M. Acosta; Fadia Sara Ceccarelli; Jaír R. Castillo; Diana Laura Batista‐Perales; Jack O. Brookhart; Paula E. Cushing (Journal of Biogeography, 2026)
Aim To assess phylogeographic structure, phylogenetic diversity and historical diversification processes in ammotrechid camel spiders from the Baja California Peninsula. Location Baja California Sur, Mexico. Time Period Miocene to Pleistocene. Major Taxa Studied Ammotrechid camel spiders (Solifugae: Ammotrechidae). Methods We conducted the first phylogeographic analysis of Baja California Sur ammotrechid camel spiders using mitochondrial COI sequences and genome‐wide RADseq data. Phylogenomic analyses, divergence dating, species accumulation curves and tests of admixture (F 3 statistics) were used to evaluate lineage structure, timing of diversification and patterns of connectivity. Results We uncovered deep phylogenomic structure and extensive cryptic diversity, identifying at least 16 putative lineages, many restricted to single localities. Divergence dating indicates Miocene origins with subsequent Plio–Pleistocene diversification. Although several lineages exhibit north–south structure, divergence times and spatial patterns do not support diversification driven by discrete transpeninsular seaway vicariance at major southern breaks (e.g., La Paz/Loreto). Instead, patterns support a model of distributed diversification shaped by tectonic segmentation, habitat heterogeneity, and climatic oscillation. Limited admixture among a subset of closely related lineages, suggested by incongruent tree topologies and F 3 statistics, indicates episodic secondary contact rather than long‐term connectivity. Species accumulation curves did not approach an asymptote, suggesting that much of the region's solifuge diversity remains undocumented. Main Conclusions Ammotrechid camel spiders preserve fine‐scale genomic signatures of landscape history in Baja California Sur and reveal previously undocumented levels of endemism and diversification. These results highlight Solifugae as promising but underused systems for geogenomic studies of desert biogeography.

High occupancy of non-native carnivores in riparian ecosystems along an urban gradient in Chile - Gisselle A. Castillo-Sandoval; José Infante-Varela; Mauricio R. Soto-Gamboa; Eduardo A. Silva-Rodríguez (Urban Ecosystems, 2026)

Reassessing the economic returns of diverse traditional agricultural systems for smallholder farmers: a case study of the milpa in Mexico - Julio Díaz-José; Rogelio Limón-Rivera; Otto R. Leyva-Ovalle; Leticia Myriam Sagarnaga-Villegas; Gregorio Briones-Ruiz; A. Carolina Elizondo-Salas; Hilario García-Martínez; Susana I. Castillo-Martínez; Pablo Andrés-Meza; Oscar Díaz-José; Francisco Guevara-Hernández; Mauricio R. Bellon (Agricultural Systems, 2026)

Confirmed Outbreaks of Streptococcosis Caused by Streptococcus agalactiae Serotype Ia in Nile Tilapia Culture From Campeche, Mexico - R. A. Avila‐Castillo; R. E. del Rio‐Rodriguez; S. A. Soto‐Rodriguez; J. Navarro‐Flores; A. D. Cu‐Escamilla; F. I. Marrujo‐Lopez; K. G. Aguilar‐Rendon; M. I. Gomez‐Solano (Journal of Fish Diseases, 2026)
Streptococcus agalactiae was confirmed as the etiologic agent of streptococcosis in Nile tilapia ( Oreochromis niloticus ) from Campeche, Mexico, during a cross‐sectional investigation of eight semi‐intensive farms (2021–2022) that yielded virulent strains in a challenge assay. Standard bacteriology, histopathology, API‐20 Strep phenotyping, one‐step PCR, and real‐time PCR confirmed S. agalactiae in five farms (62.5%). Gross and histological lesions were characterised by mid‐axial and peduncular muscle abscesses, extensive myonecrosis, granuloma formation, polyserositis, and occasional suppurative meningitis. Experimental infections fulfilled Koch's postulates. Juveniles of O. niloticus (20 g) infected with strain ASG‐2290 at 10 6 CFU/mL produced 53% mortality at 96 h. Whole‐genome sequencing of the strains ASG‐2290 and ASG‐2292 identified them as S. agalactiae Ia, marking the first report of this serotype isolated from farmed tilapia in Mexico. Frequent interstate fry movements are likely to be a risk factor for pathogen dissemination. These findings document the geographic expansion of pathogenic S. agalactiae into the Yucatan Peninsula, underscoring the need for strengthened surveillance, biosecurity, and diagnostic capacity to mitigate economic losses in Mexican tilapia aquaculture. Considering that tilapia aquaculture is carried out all year‐round in the Yucatan Peninsula, the implications of these findings are of major concern.

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

Continent-wide stock structure and connectivity of silver trevally (Pseudocaranx georgianus) based on population genomics and otolith shape and chemistry - Zoriana H.T. Lam; John Stewart; Jonathan Sandoval-Castillo; Patrick Reis-Santos; Rhiannon A. Van Eck; Bronwyn M. Gillanders; Peter Ritchie; Maren Wellenreuther; Charlie Huveneers; David V. Fairclough; Ashley M. Fowler; Julian Hughes; et al. (Fisheries Research, 2026)

Ancient and recent soils as indicators of the genesis and evolution of Salada de Chiprana from middle Pleistocene to present (Ebro Basin, NE Spain) - M. Tierra; C. Castañeda; F.J. Gracia; R. Rodríguez-Ochoa; J.R. Olarieta; A. Medialdea; O. Castillo (CATENA, 2026)

Natural forest conversion to exotic pine plantations induces soil mineralogical and physicochemical changes – implications for soil organic carbon stabilization - P. Castillo; M.F. Albornoz; O. Crovo; A. Atenas; C.I. Czimczik; R. Southard; F. Aburto (CATENA, 2026)

Revisiting Strategies for Bacterial Enumeration: The Case for Viable but Nonculturable (VBNC) Cells in Supplement Products - T. O. Kirby; J. R. Townsend; E. D. Walts; A. Kiefer; J. Zhu; M. Cormier; D. Pathak; C. Wong; A. Castillo; J. Ochoa-Repáraz; R. Jäger; R. H. Lai; et al. (Probiotics and Antimicrobial Proteins, 2026)

Cultural Importance of Asteraceae for Beekeeping and Traditional Medicine in the Yucatan Peninsula Region, Mexico - Justo R. Enríquez-Nolasco; William Cetzal-Ix; Iván Tamayo-Cen; Saikat Kumar Basu; Fernando Casanova-Lugo; Benito B. Dzib-Castillo (The Botanical Review, 2026)

Spatial heterogeneity in mussel larval abundance across fjord systems of northern Chilean Patagonia - Felipe I. Torres; Carlos Lara; Carlos Molinet; Nicole Castillo-Villagrán; Bernardo R. Broitman (Journal of Marine Systems, 2026)

Petrogenesis of the volcanic glass from the Central Lau Basin: Insight into the nature of underlying upper mantle - Xiongyue Li; Xijun Liu; Zhenglin Li; Liyan Tian; Paterno R. Castillo; Hongxia Yu; Yuzhen Liu; Xiangsong Wang (Journal of Asian Earth Sciences, 2026)

Vitamin B12 improves skeletal muscle mitochondrial biology in aged mice - Abigail R. Williamson; Angad Yadav; Wenxia Ma; Susan Schmitt; Shelby Rorrer; Lauren E. Odom; Luisa F. Castillo; Chloe T. Purello; Olga V. Malysheva; James Mobley; Martha Field; Anna E. Thalacker-Mercer (GeroScience, 2026)
Age-related skeletal muscle deterioration is a commonly reported disability among older adults, attributed to several factors including mitochondrial dysfunction, a major hallmark of aging. Therapies to attenuate or reverse mitochondrial decline are limited. Despite identified positive relationships between vitamin B12 (B12) and mitochondrial biology, the impact of B12 supplementation on skeletal muscle mitochondria, in advanced age, has not been examined. Thus, the impact of B12 supplementation on skeletal muscle mitochondrial biology was examined in aged female mice, given 12 weeks of B12 supplementation (SUPP) or vehicle control. In the mouse model, mitochondrial DNA and content were measured with PCR and citrate synthase activity, respectively; mitochondrial morphology was examined using transmission electron microscopy; mitochondrial function was examined using extracellular metabolic flux analysis; and proteins and pathway enrichment was identified with proteomics. The results demonstrated that SUPP in aged mice increased muscle mitochondrial content and improved morphology. Further, differentially expressed proteins were enriched in TCA cycle, OXPHOS, and oxidative stress pathways. This is the first study, to our knowledge, examining the impact of B12 supplementation on skeletal muscle mitochondrial biology in aged female mice. Results suggest that B12 supplementation improves mitochondrial biology in aged female mice.

Strengthening national genebanks through genomics and regional collaboration: Lessons from Latin America and the Caribbean - M. Carvajal-Yepes; C. Petroli; M. Correa; F. Breseghello; G. Tapia; E. Salazar; A. Chassaigne; M. Ferreyra; P.H. Reyes-Herrera; M. Guzmán; A. Mendoza; R. Vidal; et al. (Global Food Security, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Impact of waves on phytoplankton activity on the Northwest European Shelf: insights from observations and km-scale coupled models - Dale Partridge; Ségolène Berthou; Rebecca Millington; James R. Clark; Lucy Bricheno; Juan Manuel Castillo; Julia Rulent; Huw Lewis (Ocean Science, 2026)
The spring bloom is an annual event in temperate regions of the North Atlantic Ocean where the abundance of photosynthetic plankton increases dramatically. The timing and intensity of the spring bloom is dependent on underlying physical conditions that control ocean stratification and mixing. Although surface waves can be an important source of turbulent kinetic energy to the surface mixed layer, they have seldom been considered explicitly in studies of bloom formation. Here, we investigate the role of surface waves in bloom formation using a combination of satellite observations and numerical models. Satellite observations show a positive correlation between wave activity and chlorophyll concentration in the Northwest European shelf (May–September). In the deeper Northeast Atlantic, increased wave activity correlates with lower chlorophyll during periods of high phytoplankton activity (March-May) and higher chlorophyll when activity is low (below 54° N, July–September). We use a first-of-its-kind, km-scale, two-way coupled ocean-wave model system to investigate both the relationship between wave-driven mixing and bloom formation, and the sensitivity of model results to the method by which wave-driven mixing is parameterised. In deep regions, during the spring bloom, a wave-driven mixing event is likely to mix surface chlorophyll to deeper layers, away from light. In contrast, when phytoplankton activity is low in deep regions, wave-driven mixing can entrain nutrients, fueling the growth of nutrient starved phytoplankton near the surface. In June–October, in shallow but weakly stratified regions of the shelf, surface chlorophyll tends to be elevated following a wave-driven mixing event, which can bring to the surface both phytoplankton and nutrients from deeper layers. When contrasted with ocean-only runs, the two way-coupled ocean-wave model tends to produce greater vertical mixing and a delay in bloom onset. These results indicate bloom dynamics are sensitive to the way in which waves are modelled, and that the role of waves in bloom formation should be considered in future studies.

Dynamics of coastal picoeukaryote communities in response to oil spill disturbances - B. Glasner; I. Morel-Letelier; E. Osses; C. Galvez-Aracena; P. Ávila-Guerrero; C. Henríquez-Castillo; E. Urrejola-Pulido; C.B. Pareja; A.A. Durán; N. Trefault; R. De la Iglesia (Marine Environmental Research, 2026)

Metrics of soil degradation by recent filling of permanent gullies: a study case on annual rainfed crops at the Campiña landscape (Spain) - Carlos Castillo; Encarnación V. Taguas; Miguel Vallejo; Rafael Pérez; Robert R. Wells; Ronald L. Bingner; Helena Gómez-MacPherson (Precision Agriculture, 2026)

Sex matters: female black corals experience higher stress under different current velocities - L. Palacios-Castillo; S. Navarro-Mayoral; M. Godefroid; C. García-Herrera; F. Tuya; R. Haroun; F. Otero-Ferrer (Coral Reefs, 2026)
Black coral forests play a vital role in mesophotic and deep-water environments, providing habitat and refuge for numerous organisms. Their presence and distribution are influenced by hydrodynamic conditions. Yet, insight into the effect of current velocity on the survival and overall condition of black corals, and how this may differ between sexes during the reproductive period, is lacking. Here, we investigated how the current velocity affected male and female nubbins of Antipathella wollastoni , throughout a 5-week experiment, under three treatments: no (0 cm s −1 ), low (mean ± SE = 5.3 cm s −1 ± 0.27) and high current (10 cm s −1 ± 0.42). We studied both the nubbin state ( i.e. mortality, tissue necrosis and propagule production) and their physiology ( i.e. total antioxidant capacity, TAC). We found higher tissue necrosis and mortality in the no-current treatment. Responses were significantly sex-conditioned across all treatments. All male nubbins survived the experiment and exhibited minimal tissue necrosis (mean ± SE = 4.72% ± 0.77), whereas 33.3% of female nubbins died and showed significantly higher tissue necrosis (37.05% ± 8.57). Propagule release was up to fourfold higher under high current compared to low, whereas nubbins in the no-current treatment produced almost none, likely due to the rapid onset of necrosis preventing the use of this escape response. The findings emphasize the importance of current velocities to rear black corals under controlled conditions, especially given the increased vulnerability of female nubbins during the reproductive period.

Sex-specific nutritional requirements of mating in insects with contrasting mating systems - C. Ruth Archer; Matthew R. Carey; Charles E. Grant; Clarissa House; Amy Molotoks; Enrique del Castillo; Zeya Wagner; John Hunt (Animal Behaviour, 2026)

A hydrological model to assess current and future freshwater availability: application to climate change impacts on hydrology in the Amazon River Basin through mid-century - Silvia R. Santos da Silva; Fekadu G. Moreda; Fernando Miralles-Wilhelm; Alexandra Moreira; Stephan von Borries; Fernando Cisneros; Raul Munoz-Castillo; Paula Roberts; Raphael Payet-Burin; Silvio Pereira-Cardenal; Eveline Vasquez Arroyo (Journal of Hydrology, 2026)

Revisiting Small‐Scale Aquaculture ( SSA ) - Liliana Sierra Castillo; Halley E. Froehlich; Jono R. Wilson; Jessica A. Gephart; Erendira Aceves‐Bueno; Steven D. Gaines (Reviews in Aquaculture, 2026)
Aquatic foods are a vital source of nutrition, yet growing demand and stagnant wild‐capture fisheries have positioned aquaculture as essential to meeting global food needs. Despite this, aquaculture's diverse forms remain poorly understood, particularly small‐scale aquaculture (SSA). Unlike small‐scale fisheries (SSF), which are widely recognized in policy and research, SSA lacks consistent definitions and is often conflated with SSF or defined narrowly by physical metrics like farm size. This limits its visibility in policy and development efforts, overlooking critical social, economic, and governance dimensions such as ownership, labor, and market orientation. Through a systematic review of 83 studies across 24 countries, we analyze SSA across ecosystems (freshwater, brackish, marine) and species groups (finfish, invertebrates, seaweed) to identify trends in production characteristics, yield reporting, and social dimensions. We find freshwater SSA dominates the literature, while marine SSA, especially mollusk farming, is significantly underrepresented. SSA exhibits wide variation in yields, farm sizes, ownership, and management structures, indicating that existing classification frameworks are insufficient. We propose a context‐sensitive, social‐ecological classification system that integrates production metrics with governance and socioeconomic characteristics. To guide application, we offer two policy frameworks, one for regions with existing SSA definitions, recommending participatory revision and expanded data collection; and one for regions without definitions, advocating for a stepwise approach to characterization. Our findings underscore the need for more inclusive, adaptable classifications to improve SSA's visibility in global food policy and unlock its full contributions to sustainable development, equity, and local livelihoods.

Molecular phylogenetics, geometric morphometrics and character assessment support the reinstatement of the Southern Andean Yungas sage Salvia alba (Lamiaceae) - Santiago Castillo; Itzi Fragoso-Martinez; Dana L. Aguilar; Manuel I. Stefanini; Juliana V. Izquierdo; John R. I. Wood; Santiago Benitez-Vieyra (Systematics and Biodiversity, 2025)

Infrared Emission in the Second Biological Window in LaInO3:Ho3+ Exciting in the First Biological Window - Mauricio A. Vega-Pallauta; Rodrigo Castillo; Kevin Soler-Carracedo; Inocencio R. Martin (Journal of Fluorescence, 2025)

Functional characterization of splice variants in hereditary breast and ovarian cancer susceptibility genes - Laura Rosado-Jiménez; Younes Mestre-Terkemani; Ángeles García-Aliaga; María D. Sarabia-Meseguer; Miguel Marín-Vera; José A. Macías-Cerrolaza; Pilar Sánchez-Henarejos; María R. García-Hernández; Marta Zafra-Poves; Beatriz C. Álvarez-Abril; Carmen B. López-Sánchez; María P. Moya-Martínez; et al. (Familial Cancer, 2025)

Philippine functional foods: A new frontier in noncommunicable diseases prevention - Myra O. Villareal; Lotis E. Mopera; Gladys C. Completo; Ruel C. Nacario; Marissa V. Romero; Katherine Ann T. Castillo-Israel; Rona Camille M. Lizardo-Agustin; Marianne Joy G. Laya; Roi Miguel M. Obdosantos; Christel Leo O. Romano; Jocelyn E. Serrano; Samuel C. Bobiles; et al. (Food and Humanity, 2025)

Enhancing wheat yield (Triticum durum Desf.) through the application of TiO2, ZnO, FexOx, and Ag nanoparticles to agricultural land - Andrés Torres-Gómez; César R. Sarabia-Castillo; Gabriela Guillen-Cruz; Fabián Fernández-Luqueño (Cereal Research Communications, 2025)
As the world’s population continues to grow, the demand for food is also rising. To meet this demand, the Food and Agriculture Organization (FAO) has proposed using nanoparticles (NPs) as a new tool for agriculture. Compared to traditional agrochemical fertilizers, NPs are more efficient and environmentally friendly. Studies have shown that NPs can improve soil quality and increase crop yields. To evaluate the effectiveness of four types of NPs–TiO 2 , ZnO, Fe x O x , and Ag–on the properties of a Samayoa C2004 wheat crop, a field experiment was conducted in southeastern Coahuila state, Mexico. The experiment involved planting a dose of 140 kg ha −1 in plots of 9 m 2 (divided by 6 m 2 borders), with a dose of NPs set at 200 g ha −1 . The data was analyzed using a one-way ANOVA and Tukey test ( p ≤ 0.05) in Minitab18 software. The study results showed that the ZnO–NPs treatment increased the yield compared to the values reported by Mexico’s National Institute for Forestry, Agriculture and Livestock Research (INIFAP) in the same cycle. The soil biomass was also increased compared to the other treatments, which is attributed to the beneficial properties of the ZnO-NPs. In conclusion, this study found that ZnO-NPs were the most effective treatment for improving soil quality and increasing wheat yield under field conditions in semiarid soil.

Thrips (Insecta: Thysanoptera) species associated with avocado orchards in central Veracruz, Mexico - David Alarcón-Utrera; Daniel López-Lima; Carlos R. Cerdán-Cabrera; Gerardo Alvarado-Castillo; Alejandro Salinas-Castro; Gloria Carrión (International Journal of Tropical Insect Science, 2025)

Recovery of strategic elements from mining tailings at La Cienega, Peru, through geochemical and mineralogical assessment: a focus on circular economy policy - Marco A. Cotrina-Teatino; Jairo J. Marquina-Araujo; Jose N. Mamani-Quispe; Jorge Chira-Fernandez; Cesar De la Cruz-Poma; Aldo R. Castillo-Chung; Solio M. Arango-Retamozo; Joe A. González-Vasquez; Salomon M. Ortiz-Quintanilla (Resources Policy, 2025)

Effect of a feed additive based on a mix of condense and hydrolysable tannins (ByPro®) on lactating dairy cows milk production performance - Alejandro R. Castillo; Martin Pol; Mónica Gaggiotti; Julio A. Di Rienzo; Damiano Cavallini (Tropical Animal Health and Production, 2025)
The objective of this research was to evaluate the effect of a commercial mix of condensed and hydrolysable tannins feed additive to lactating dairy cows. Two high-scale dairy farm units, similar management and diets were used. All lactating cows in one unit were fed with the mix of tannins (ByPro ® 0.3%DMI), the other unit was the Control. Cows were categorized per DIM, 0 to 30, 31 to 120, 121 to 365, and more. Milk yield and composition was evaluated in all the lactating cows in each dairy unit at time 0, (initial), and after 4 weeks of supplementation (final). A linear model was adjusted for each variable. Estimated DMI and diets were similar in both dairy units, averaging 25.5 kg DMI/cow, as well as feed ingredients, dietary nutrient contents, and milk yield (34 kg milk/cow per day). Milk yield, from 0 to 365 DIM was increased ( P < 0.01) on supplemented cows (+ 2.3 ± 0.33 L milk/cow.d), with no effect on milk fat and protein contents. High data variability was observed on cows with 0–30 DIM, milk fat and protein content were reduced by ByPro without effect on milk yield. Positive responses of ByPro ® on milk, milk fat and protein contents from 31 to 120 and 121–365 DIM were observed, + 3.6 and + 3.2 kg milk/cow.d; +0.27% fat and + 0.21% protein; and + 0.17% fat, + 0.11% protein; respectively. The mix of tannins increased milk lactation performance on cows with more than 30 DIM.

Origin of the Daly gap - Paterno R. Castillo (Science Bulletin, 2025)

Strategic potential assessment of lanthanum and scandium through geochemical-lithological analysis with unsupervised machine learning in southern Ecuador - Marco A. Cotrina-Teatino; Jairo J. Marquina-Araujo; Jose N. Mamani-Quispe; José A. Guartán; Aldo R. Castillo-Chung; Solio M. Arango-Retamozo; Joe A. González-Vasquez; Salomon M. Ortiz-Quintanilla (Resources Policy, 2025)

Onychocolone A produced by the fungus Onychocola sp. targets cancer stem cells and stops pancreatic cancer progression by inhibiting MEK2-dependent cell signaling - Maria C Ramos; Gloria Crespo-Sueiro; Nuria de Pedro; Carmen Griñán-Lisón; Caridad Díaz; Víctor González-Menéndez; Francisco Castillo; Jose R Tormo; Olga Genilloud; Fernando Reyes; Rosario Fernández-Godino (Phytochemistry Letters, 2025)

Nutrition Assessment in Cyclic Vomiting Syndrome: Exploring the Prevalence of Avoidant/Restrictive Food Intake Disorder, Disordered Eating, and Metabolic Dysregulation - L. Forsthoefel; G. Vanhouwe; O. Khan; K. Heitman; K. Goheen; E. Holley; P. Madril; J. Kennel; R. Jimenez-Castillo; S. Arumugam; M. Vyas; P. Goday; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Geochemical and mineralogical characterization of critical elements in gold tailings from the La Cienega, Peru, and assessment of their reuse potential - Marco A. Cotrina-Teatino; Jairo J. Marquina-Araujo; Jose N. Mamani-Quispe; Jorge E. Chira-Fernandez; Aldo R. Castillo-Chung; Solio M. Arango-Retamozo; Joe A. González-Vasquez; Salomon M. Ortiz-Quintanilla (Journal of Environmental Chemical Engineering, 2025)

Long-Term Treatment with Alcaligenes faecalis A12C Improves Host Resistance to Pathogens in Septic Rats: Possible Contribution of Curdlan-Like Immune Trainer - C. J. Martel-Benítez; R. Alayón-Afonso; D. Padilla Castillo; F. J. Chamizo-López; M. Isabel García-Laorden; A. Espinosa de los Monteros y Zayas; J. C. Rivero-Vera; P. Nogueira Salgueiro; F. Real; A. Bordes-Benítez; A. Martel Quintana; C. Almeida Peña; et al. (Probiotics and Antimicrobial Proteins, 2025)
Curdlan, a β-1,3/1,6-glucan found in Alcaligenes faecalis ( A. faecalis ) wall, activates innate and humoral immunity. The aim of this study is to evaluate whether pretreated rats with A. faecalis A12C could prevent sepsis disturbances and identify the immunomodulatory mechanisms involved. Experiments occurred in two stages: a survival study with 16 rats randomly divided into septic (SC) ( n = 8) and septic pretreated (SA) ( n = 8) groups and 45 rats divided into four groups: healthy (AGUSAN) ( n = 9), septic (AGUIC) ( n = 13), septic pretreated (AGUIA) ( n = 14), and healthy pretreated (AGUSTO) ( n = 9). Sepsis was induced by cecal ligation and puncture after 30 days of A. faecalis A12C pretreatment or without. SA group had a higher survival rate of 58% vs. 16% for SC group ( P < 0.05). Overall, AGUIA showed better status than AGUIC ( P < 0.01). Higher monocytosis was found in AGUIA and AGUSTO vs. AGUIC and AGUSAN, respectively ( P < 0.05). A gradual increase in curdlan fecal concentration was observed in AGUIA during pretreatment. Fecal concentrations of Escherichia coli significantly decreased in AGUIA and AGUSTO. Bacterial load in urine, peritoneal lavage fluid (PLF), and bronchoalveolar lavage fluid (BALF) decreased ( P < 0.05) in AGUIA vs. AGUIC. Finally, lower inflammation was observed in serum, BALF, and PLF, with reduced IL-6, IL-10, IL-1β, and TNF-α, along with less damage in lungs and peritoneum in AGUIA vs. AGUIC. These findings suggest the connection between curdlan—produced by A. faecalis A12C—with the immune system and the reduction in severity of experimental sepsis.

Cardiovascular risk of gender-affirming estrogen therapy in a transgender rat model - D. S. Escudero; V. R. Martínez; Y. Pirosanto; G. A. Colareda; M. Pis Diez; J. M. Lofeudo; O. Castillo; J. O. Vélez Rueda; E. L. Portiansky; N. G. Pérez; R. G. Díaz (Journal of Molecular Medicine, 2025)

Effects of synthetic estrogen (17α-ethynylestradiol) on spawning in the aggregating anemone, Anthopleura elegantissima, and density and photosynthetic performance of its zooxanthellae symbiont, Breviolum muscatinei - Lisa T. Crummett; Sebastian R. Castillo (Aquatic Sciences, 2025)
The effect of estrogenic pollutants on wildlife is a growing concern. Synthetic estrogen, 17α-ethynylestradiol (EE2), is a potent estrogenic pollutant used in birth control that originates in wastewater and ends up in receiving surface waters where it can accumulate in sediments and aquatic organisms. EE2 can reduce growth, gametogenesis, semen quality, fecundity, and embryo viability and promote feminization and skewed sex ratios among different aquatic organisms. Most research on EE2 impacting aquatic life has focused on fish, with less attention paid to invertebrates and algae. We examine the effect of environmentally relevant concentrations of EE2 (0, 1.5, 15, and 150 ng/l) on spawning in males of the aggregating anemone, Anthopleura elegantissima , and density and photosynthetic performance of its zooxanthellae symbiont, Breviolum muscatinei . Exposure to 150 ng/l EE2 significantly increased chlorophyll a content per zooxanthellae cell and photosynthetic efficiency (F v /F m ) of Photosystem II compared to the negative control. Symbiont density was not significantly associated with EE2 concentration, whereas host clonality was significantly associated. Lastly, EE2 concentration was a significant predictor of whether anemones spawned after being induced. This is the first study to our knowledge to examine the impact of EE2 exposure on anemone spawning and zooxanthellae density and photosynthetic performance.

Impacts of heat stress under oceanic climate on fertility and reproductive physiology of dairy cows subjected to hormonal synchronization - E. N. Martínez; C. Castillo; L. Avendaño-Reyes; J. Hernández; J. L. Benedito; A. Rico; P. Garcia; R. Muiño (International Journal of Biometeorology, 2025)
Regions with oceanic climates are experiencing unprecedented climatic changes. This study assesses the presence of heat stress in these regions and its impact on reproductive in Holstein cows using the Temperature-Humidity Index (THI), a measure of thermal stress. Data was collected from 159 Holstein cows across experiments. Cows underwent a modified double-ovsynch synchronization protocol, while 96 cows were inseminated based on observed estrous. Cows were examined for body temperature, follicle and uterus examination, and serum progesterone concentrations to evaluate the impact of heat stress. The results of cows pregnancy rate in double-ovsynch synchronized cows were 48.5% and 43.3% in summer and winter seasons, respectively. While the pregnancy rate in non-synchronized cows were 29.5% and 32.7% in summer and winter season, respectively. Elevated THI levels (THI ≥ 72) have adversely effects on reproductive physiology, reduced estrous expression, decreased uterine blood flow, and altered progesterone concentrations. Mild heat stress during summer months in oceanic climate negatively impacted reproductive efficiency in dairy cows, for adaptive management strategies. The double-ovsynch protocol effectively stabilized fertility across seasons, demonstrating its value in improving reproductive outcomes under varying thermal conditions.

Cross-canyon variability in zooplankton backscattering strength in a river-influenced upwelling area - Macarena Díaz-Astudillo; Manuel I. Castillo; Pedro A. Figueroa; Leonardo R. Castro; Ramiro Riquelme-Bugueño; Iván Pérez-Santos; Oscar Pizarro; Gonzalo S. Saldías (Ocean Science, 2025)
Zooplankton are a key component of food webs in upwelling systems. Their distribution is influenced not only by mesoscale and climate dynamics but also by topography and local currents. Submarine canyons that incise the continental shelf can act as conduits, transporting deep, nutrient-rich waters to shallower regions and promoting coastal biological productivity. Consequently, these canyons facilitate the advection and accumulation of zooplankton. We aimed to describe the spatio-temporal variability in zooplankton distribution (using net samples and acoustic data) and their association with local currents in a long, narrow submarine canyon located in the highly productive continental shelf off central Chile. The backscattering strength (Sv), a proxy for zooplankton biomass, was highly variable on both diurnal and spatial scales. Higher Sv and abundances were found at night, following the classic diel vertical migration pattern. Zooplankton were not uniformly distributed within the canyon. In the surface and mid-depth layers, the canyon walls accumulated more zooplankton than the center, particularly during the nighttime. Within the canyon, the currents were asymmetrical and frequently reversed direction. When the positive along-canyon current was stronger on the northern slope, Sv was also higher on that wall. This pattern was especially evident in the section closer to the canyon head. We show that the Biobio Canyon is a highly dynamic environment where oceanographic conditions can rapidly shift. Our findings suggest a feasible mechanism for zooplankton retention driven mainly by along-canyon flow asymmetry and vertical migrations.

Bovine oocyte vitrification and recovery with ethylene glycol and either propylene glycol or dimethyl sulfoxide - Ashlyn Brewer; Emily Girka; Ashton Dalton; Emilio Gutierrez-Castillo; Kenneth R. Bondioli (Theriogenology, 2025)

Chronic arsenic exposure of ovarian surface and fallopian tube cultures induces giant and/or multinucleated cells with phagocytosis-like properties and an inflammatory phenotype - Cristina M. Andrade-Feraud; Arlet M. Acanda de la Rocha; Noah E. Berlow; Santiago Duque; Alexander Velazco; Diego Castillo; Baylee Holcomb; Ebony R. Coats; Yasmin R. Ghurani; Catherine M. Lucey; Brandon Pearson; Tomás R. Guilarte; et al. (Toxicology and Applied Pharmacology, 2025)

Comparative study of the physicochemical properties of metal organic frameworks in the adsorption of textile dyes - A. N. Pérez-Jasso; I. A. Aguayo-Villarreal; C. K. Rojas-Mayorga; R. Muñiz-Valencia; D. I. Mendoza-Castillo; A. Bonilla-Petriciolet (International Journal of Environmental Science and Technology, 2025)

One well-planned and executed exchange is better than two: Lessons learned from a reciprocal fisheries learning exchange between Madagascar and Mexico - Katie R. Thompson; Steve Rocliffe; Alejandro Castillo López; Tinah Martin; S. Hoyt Peckham; Christian Portillo; Xavier Vincke; Lekelia D. Jenkins (Marine Policy, 2025)

Safety Outcomes of Antiplatelet Therapy During Endovascular Treatment of Tandem Lesions in Acute Ischemic Stroke Patients - Mudassir Farooqui; Afshin A. Divani; Milagros Galecio-Castillo; Ameer E. Hassan; Mouhammad A. Jumaa; Marc Ribo; Michael Abraham; Nils Petersen; Johanna Fifi; Waldo R. Guerrero; Amer M. Malik; James E. Siegler; et al. (Translational Stroke Research, 2025)

Unraveling the lab-scaling up production of activated carbon from plastic-enriched waste - Ledicia Pereira; Gabriel Blázquez; Ventura Castillo; Francisco Miguel González-Pernas; María González-Lucas; M. Ángeles Martín-Lara; Mónica Calero; Rafael R. Solís (Journal of Cleaner Production, 2025)

Unveiling the diversity of macrobenthic crustaceans on sandy beaches of the eastern Mexican coast: new records and an updated checklist - María R. Muciño-Reyes; Edlin Guerra-Castro; Raúl E. Castillo-Cupul; Carlos E. Paz-Ríos; Nuno Simões (Frontiers in Marine Science, 2025)
Despite the ecological importance of sandy beaches, the diversity and distribution of macrocrustacean communities in the eastern Mexican coast (Mexican coast of the Gulf of Mexico and Caribbean Sea) remain understudied. As the first large-scale sampling effort along the eastern Mexican coast, this study aimed to estimate macrocrustacean diversity and evaluate sampling methodologies, while providing historical context for macrocrustacean research in the region. Two sampling designs using sediment cores (4 versus 6 cores per transect) were implemented across 15 sandy beaches. A total of 3,352 organisms were collected, representing 22 species from 17 genera, spanning 14 families, 7 suborders, 5 orders, and 2 superorders. Amphipoda and Isopoda exhibited the highest species richness and abundance. The study yielded seven new geographical records ( Haustorius jayneae , Rhepoxynius epistomus , Americorchestia salomani , Heterodina mosaica , Cassidinidea ovalis , Exosphaeroma diminutum , and Sphaeroma walkeri ). Results demonstrated that the 6-core sampling design provided better diversity representation. An updated checklist comprising 77 species/taxa for the eastern Mexican coast was compiled, integrating historical and new data. This comprehensive assessment enhances our understanding of these vulnerable ecosystems and emphasizes the need for broader temporal and spatial scale studies to inform effective conservation strategies.

Shortfalls in the protection of Important Shark and Ray Areas undermine shark conservation efforts in the Central and South American Pacific - Théophile L. Mouton; Adriana Gonzalez-Pestana; Christoph A. Rohner; Ryan Charles; Emiliano García-Rodríguez; Peter M. Kyne; Amanda Batlle-Morera; Giuseppe Notarbartolo di Sciara; Asia O. Armstrong; Enzo Acuña; Joanna Alfaro-Shigueto; Randall Arauz; et al. (Marine Policy, 2025)

Widespread pharmaceutical exposure at concentrations of concern for a subtropical coastal fishery: Bonefish (Albula vulpes) - N.A. Castillo; R.O. Santos; W.R. James; R. Rezek; D. Cerveny; R.E. Boucek; A.J. Adams; J. Fick; T. Brodin; J.S. Rehage (Marine Pollution Bulletin, 2024)

Green coffee extracts microencapsulated by spray freezing into the liquid cryogenic - Jaime López-Domínguez; Maria Teresa González-Arnao; Cesar A. Ortíz-Sánchez; Marisol Castillo-Morales; Martha P. Rascón-Díaz; Ubaldo R. Marin-Castro (Cryobiology, 2024)

A holistic simulation model of solid-set sprinkler irrigation systems for precision irrigation - M. Morcillo; J. F. Ortega; R. Ballesteros; A. del Castillo; M. A. Moreno (Precision Agriculture, 2024)

Correction: DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew Dewoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)

DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew DeWoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)
Genetic diversity is essential for maintaining healthy populations and ecosystems. Several approaches have recently been developed to evaluate population genetic trends without necessarily collecting new genetic data. Such “genetic diversity indicators” enable rapid, large-scale evaluation across dozens to thousands of species. Empirical genetic studies, when available, provide detailed information that is important for management, such as estimates of gene flow, inbreeding, genetic erosion and adaptation. In this article, we argue that the development and advancement of genetic diversity indicators is a complementary approach to genetic studies in conservation biology, but not a substitute. Genetic diversity indicators and empirical genetic data can provide different information for conserving genetic diversity. Genetic diversity indicators enable affordable tracking, reporting, prioritization and communication, although, being proxies, do not provide comprehensive evaluation of the genetic status of a species. Conversely, genetic methods offer detailed analysis of the genetic status of a given species or population, although they remain challenging to implement for most species globally, given current capacity and resourcing. We conclude that indicators and genetic studies are both important for genetic conservation actions and recommend they be used in combination for conserving and monitoring genetic diversity.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Superhydrophobic coatings reduce human bacterial foodborne pathogen attachment to woods used in fresh produce harvest and postharvest packing - Zachariah Vice; William de Florio; Joseph Masabni; Luis Cisneros-Zevallos; Alejandro Castillo; Chris R. Kerth; Mustafa Akbulut; Thomas M. Taylor (Food Microbiology, 2024)

Overlapping hotspot tracks and melts from diffuse plume materials in the upper mantle generated intraplate seamount groups in the West Pacific - Xun Wei; Guo-Liang Zhang; Ji Zhang; Xue-Fa Shi; Paterno R. Castillo; Yan Zhang; Wan-Feng Zhang; Yi-Gang Xu; Hong-Yan Li; Hui Zhang (Earth and Planetary Science Letters, 2024)

Connecting the dots: Applying multispecies connectivity in marine park network planning - Katie Gates; Jonathan Sandoval-Castillo; Andrea Barceló; Andrea Bertram; Eleanor A.L. Pratt; Peter R. Teske; Luciana Möller; Luciano B. Beheregaray (Biological Conservation, 2024)

Differential tissue distribution of pharmaceuticals in a wild subtropical marine fish - N.A. Castillo; R.O. Santos; W.R. James; R. Rezek; D. Cerveny; R.E. Boucek; A.J. Adams; J. Fick; T. Brodin; J.S. Rehage (Aquatic Toxicology, 2024)

Gut colonization by extended-spectrum β-lactamase-producing Escherichia coli in dairy herd in Brazil: successful dissemination of a One Health clone - Luciana Sartori; Fábio P. Sellera; Taiana T. Silva-Pereira; Bruna Fuga; Danny Fuentes-Castillo; Milena Dropa; Quézia Moura; Miriam R. Fernandes; Larissa Rodrigues; Fernanda Esposito; Elder Sano; Mario A. R. Aleman; et al. (Veterinary Research Communications, 2024)

P18-09 Quantitative analysis of micro and nanoplastics in biological tissues: implications for environmental and human health - M. Garcia; A. Nihart; R. Liu; E. El Hayek; E. Castillo; B. Bleske; E. Barrozo; M.A. Suter; J. Scott; K. Forsythe; N. Adolfi; D. Gallego Umana; et al. (Toxicology Letters, 2024)

Development and characterization of a novel variant of long-acting bovine follicle-stimulating hormone (brscFSH) - Oscar Ignacio Cabeza; Natalie Parra; Rita Cerro; Rodrigo Mansilla; Roxana Zuniga Sanchez; Miguel Gutierrez-Reinoso; Eduardo H. Escribano; Raul Castillo; Lleretny Rodriguez-Alvarez; Kaio Tavares; Saul Gaudencio; Leonardo Martins; et al. (Theriogenology, 2024)

Identifying pathways of pharmaceutical exposure in a mesoconsumer marine fish - N.A. Castillo; W.R. James; R.O. Santos; R. Rezek; D. Cerveny; R.E. Boucek; A.J. Adams; S. Trabelsi; A. Distrubell; M. Sandquist; J. Fick; T. Brodin; et al. (Journal of Hazardous Materials, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Key energy metabolisms in modern living microbialites from hypersaline Andean lagoons of the Salar de Atacama, Chile - Jorge R. Osman; Julio Castillo; Vilma Sanhueza; Ana Z. Miller; Alexey Novoselov; Davor Cotoras; Daniela Morales (Science of The Total Environment, 2024)

Between conflict and reciprocal habituation: Human-wild boar coexistence in urban areas - Carles Conejero; Carlos González-Crespo; Jaume Fatjó; Raquel Castillo-Contreras; Emmanuel Serrano; Santiago Lavín; Gregorio Mentaberre; Jorge R. López-Olvera (Science of The Total Environment, 2024)

Genetic (co)variation for resistance to white spot syndrome virus, acute hepatopancreatic necrosis, and overall pond survival in Litopenaeus vannamei - Reyes López-Ordaz; Alejandra Caballero-Zamora; José M. Yáñez; Leobardo Montoya-Rodríguez; Bruno Gómez-Gil; Sonia A. Soto Rodríguez; Alfonso Martínez Ortega; Juan C. Quintana-Casares; Héctor Castillo-Juárez; Gabriel R. Campos-Montes (Aquaculture International, 2024)

Multinational evaluation of genetic diversity indicators for the Kunming‐Montreal Global Biodiversity Framework - Alicia Mastretta‐Yanes; Jessica M. da Silva; Catherine E. Grueber; Luis Castillo‐Reina; Viktoria Köppä; Brenna R. Forester; W. Chris Funk; Myriam Heuertz; Fumiko Ishihama; Rebecca Jordan; Joachim Mergeay; Ivan Paz‐Vinas; et al. (Ecology Letters, 2024)
Under the recently adopted Kunming‐Montreal Global Biodiversity Framework, 196 Parties committed to reporting the status of genetic diversity for all species. To facilitate reporting, three genetic diversity indicators were developed, two of which focus on processes contributing to genetic diversity conservation: maintaining genetically distinct populations and ensuring populations are large enough to maintain genetic diversity. The major advantage of these indicators is that they can be estimated with or without DNA‐based data. However, demonstrating their feasibility requires addressing the methodological challenges of using data gathered from diverse sources, across diverse taxonomic groups, and for countries of varying socio‐economic status and biodiversity levels. Here, we assess the genetic indicators for 919 taxa, representing 5271 populations across nine countries, including megadiverse countries and developing economies. Eighty‐three percent of the taxa assessed had data available to calculate at least one indicator. Our results show that although the majority of species maintain most populations, 58% of species have populations too small to maintain genetic diversity. Moreover, genetic indicator values suggest that IUCN Red List status and other initiatives fail to assess genetic status, highlighting the critical importance of genetic indicators.

Nanoencapsulation of extracts and isolated compounds of plant origin and their cytotoxic effects on breast and cervical cancer treatments: Advantages and new challenges - Gloria A. Guillén-Meléndez; Raymundo A. Pérez-Hernández; Abelardo Chávez-Montes; Uziel Castillo-Velázquez; María de Jesús Loera-Arias; Carlos R. Montes-de-Oca-Saucedo; Humberto Rodríguez-Rocha; Flavio F. Contreras-Torres; Odila Saucedo-Cárdenas; Adolfo Soto-Domínguez (Toxicon, 2024)

Conversion of char from pyrolysis of plastic wastes into alternative activated carbons for heavy metal removal - Ledicia Pereira; Ventura Castillo; Mónica Calero; Gabriel Blázquez; Rafael R. Solís; M. Ángeles Martín-Lara (Environmental Research, 2024)

Insights into using plastic waste to produce activated carbons for wastewater treatment applications: A review - Ledicia Pereira; Ventura Castillo; Mónica Calero; Gabriel Blázquez; Rafael R. Solís; M. Ángeles Martín-Lara (Journal of Water Process Engineering, 2024)

Ecological and biochemical considerations based on stable isotope analysis of blood: A case study from two juvenile lamnid sharks - Elena Tamburin; Sora L. Kim; Fernando R. Elorriaga-Verplancken; Alberto Sánchez-González; Agustín Hernández-Herrera; Mauricio Hoyos-Padilla; José Leonardo Castillo-Geniz; Carlos Javier Godinez-Padilla; Felipe Galván-Magaña (Journal of Experimental Marine Biology and Ecology, 2024)

Monitoring surface-water connectivity in a coastal lowland river using field-based data loggers - İnci Güneralp; Cesar R. Castillo; Billy U. Hales (Journal of Hydrology, 2024)

Promoting the circular economy: Valorization of a residue from industrial char to activated carbon with potential environmental applications as adsorbents - Ledicia Pereira; Ventura Castillo; Mónica Calero; Sergio González-Egido; M. Ángeles Martín-Lara; Rafael R. Solís (Journal of Environmental Management, 2024)

Denim washing wastewater treatment by coupling coagulation–flocculation/Fe-garnet filtration: life cycle assessment and the fertilization with the sludge - Y. Robles-Bueno; L. A. Castillo-Suárez; I. Linares-Hernández; V. Martínez-Miranda; L. Garduño-Pineda; C. Alanis; R. Natividad (International Journal of Environmental Science and Technology, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Design and functional characterization of Salmo salar TLR5 agonist peptides derived from high mobility group B1 acidic tail - Aleikar Vásquez-Suárez; Carolina Muñoz-Flores; Leonardo Ortega; Francisco Roa; Carolina Castillo; Alex Romero; Natalie Parra; Felipe Sandoval; Luis Macaya; Iván González-Chavarría; Allisson Astuya; María Francisca Starck; et al. (Fish & Shellfish Immunology, 2024)

Monitoring of Chemical Species in Soils, Waters and Plants Near the Active Copper Mine Tailing Dam Ovejeria (Central Chile) - Y. Tapia; A. García; E. Acuña; O. Salazar; M. Casanova; F. Najera; C. Kremer; B. Castillo; A. Joven; O. Diaz; R. Pastene; M. Antilen; et al. (Water, Air, & Soil Pollution, 2024)

Assessing the impact of land use change on different components of plant diversity in a tropical montane cloud forest of Mexico - Gonzalo Castillo-Campos; José G. García-Franco; M. Luisa Martínez; Gabriela Vázquez; Jesús J. Pale-Pale; Mirna R. Zamudio Pérez; Octavio Pérez-Maqueo (Biodiversity and Conservation, 2024)

Understanding pharmaceutical exposure and the potential for effects in marine biota: A survey of bonefish (Albula vulpes) across the Caribbean Basin - N.A. Castillo; W.R. James; R.O. Santos; R. Rezek; D. Cerveny; R.E. Boucek; A.J. Adams; T. Goldberg; L. Campbell; A.U. Perez; J.J. Schmitter-Soto; J.P. Lewis; et al. (Chemosphere, 2024)

Microplastics on sandy beaches of Chiapas, Mexico - Khirbet López-Velázquez; Kevin G. Duque-Olivera; David A. Santiago-Gordillo; Edwin R. Hoil-Canul; Jorge L. Guzmán-Mar; Minerva Villanueva-Rodríguez; José G. Ronderos-Lara; Cesar Castillo-Quevedo; José L. Cabellos-Quiroz (Regional Studies in Marine Science, 2024)

Ontogeny of interxylary phloem and stem anatomy of the Cuban endemic Henleophytum (Malpighiaceae) - Angélica Quintanar-Castillo; Pedro A. González Gutiérrez; Marcelo R. Pace (Flora, 2024)

Effectiveness of dietary heat-killed Bacillus subtilis harboring plasmid containing 60 copies of CpG-ODN 1668 against Vibrio harveyi in Penaeus vannamei - Wahyu Purbiantoro; Vinh Huynh-Phuoc; B. R. J. Castillo-Corea; Omkar Vijay Byadgi; Ta-Chih Cheng (Veterinary Research Communications, 2024)

Exploring the potential of microbial fuel cell-assisted biodegradation of nonylphenol - E. De la Peña; C. Castillo-Zacarías; R. G. Araújo; M. Rostro-Alanis; R. Parra-Saldivar; J. Rodriguez-Rodriguez (International Journal of Environmental Science and Technology, 2024)

Detection of subsurface bruises in plums using spectral imaging and deep learning with wavelength selection - S. Castillo-Girones; R. Van Belleghem; N. Wouters; S. Munera; J. Blasco; W. Saeys (Postharvest Biology and Technology, 2024)

The effect of succinate on color stability of Bos indicus bull meat: pH-dependent effects during the 14-day aging period - Monique Marcondes Krauskopf; Chimenes Darlan Leal de Araújo; Priscila R. dos Santos-Donado; Mariana Damiames Baccarin Dargelio; João Antônio Santos Manzi; Anna Cecilia Venturini; Júlio César de Carvalho Balieiro; Eduardo Francisquine Delgado; Carmen Josefina Contreras Castillo (Food Research International, 2024)

Evaluating heavy metal levels and their toxicity risks in an urban lake in Chennai, India - D. Rosado; F. Castillo; I. Nambi; R. Sadhasivam; H. Valleru; N. Fohrer (International Journal of Environmental Science and Technology, 2024)
Many urban water bodies in Chennai, India receive untreated sewage that pollutes their waters. An example is the Sembakkam lake, in which water reaches the Pallikaranai marshland, a proposed Ramsar site. In 2019, the city experienced the worst water crisis in 30 years, and many lakes were extremely dry, favoring peaks of heavy metals. Therefore, this study focuses on analysing heavy metal pollution and evaluating its potential effects on biota. In situ parameters were measured and water, sediment, and water hyacinth samples were collected during four campaigns. Al, As, Cr, Cu, Fe, Mn, Ni, Pb, and Zn were measured in all samples. Digestions for total metal content were performed in solid samples and acetic acid extractions only in sediments. The average pH (7.89–8.46) was neutral-alkaline and electrical conductivities (1559–2864 µS/cm) were high. In water, Pb (average: 2.59 µg/l) posed the highest toxicity risk according to the United Nations Economic Commission for Europe, followed by Cu and Cr. In sediment, Cu and Cr reached severe enrichment with respect to continental crust (averages: 19.46 and 13.65) followed by Ni and Zn with moderately severe enrichment. Ni produced the highest toxicity risk (average: 76.18 mg/kg), above the effects range-median, followed by Cr and Cu, between the effects range-low and effects range-median. The highest bioaccumulation factors in the water hyacinth were in the roots. Translocation factors showed similar concentrations in stems and leaves. Proper management of sewage is necessary to diminish the potential deleterious effects of metals on aquatic life and by extension, human health.

Jute fibre reinforced biocomposite: Seawater immersion effects on tensile properties and its application in a ship hull design by finite-element analysis - Jorge Antonio Velasco-Parra; Fabuer R. Valencia; Alberto Lopez-Arraiza; Bladimir Ramón-Valencia; Germán Castillo-López (Ocean Engineering, 2023)

Diet Quality Outcomes of a Cooperative Extension Diabetes Prevention Program - Hannah K. Wilson; Isaura M. Castillo-Hernandez; Ellen M. Evans; Ewan R. Williams; Alison C. Berg (Journal of Nutrition Education and Behavior, 2023)

Application of an Fe-TAML/H2O2 system for rapid degradation of organic matter - Patricio J. Espinoza-Montero; Carolina Burneo; Amanda Cevallos; G. Xavier Castillo-Cabrera; Sofía Peñafiel-Vicuña; Carlos Martínez-Huitle; Lenys Fernández; José R. Mora (Journal of Environmental Chemical Engineering, 2023)

An alternative new view of convergent margin magmatism - Paterno R. Castillo (Journal of Asian Earth Sciences, 2023)

Petrogenesis of high-alumina basalts: Implications for magmatic processes associated with the opening of the South China Sea - Wei Wang; Liyan Tian; Paterno R. Castillo; Tao Wu; Yunpeng Dong; Hongling Liu; Lingxuan Chen (Chemical Geology, 2023)

Ecological aspects of false killer whales ( Pseudorca crassidens ) from Mexican Pacific and Southern California waters - Camila Lazcano‐Pacheco; Acilegna J. Castillo‐Sánchez; Christian D. Ortega‐Ortiz; Ibiza Martínez‐Serrano; Francisco Villegas‐Zurita; Astrid Frisch‐Jordán; Oscar R. Guzón‐Zatarain; Katherina Audley; Nicola Ransome; Jaime Bolaños‐Jiménez; Jorge Urbán‐R.; Annie B. Douglas (Marine Mammal Science, 2023)

Mathematical modeling of breakthrough curves for 8-hydroxyquinoline removal from fundamental equilibrium and adsorption rate studies - S. Aguirre-Contreras; R. Leyva-Ramos; R. Ocampo-Pérez; C.G. Aguilar-Madera; J.V. Flores-Cano; N.A. Medellín-Castillo (Journal of Water Process Engineering, 2023)

Alley cropping agroforestry systems change weed community composition and reduce dominant weed species associated with corn in southern Mexico - Fernando Casanova-Lugo; Luis A. Lara-Pérez; Benito Dzib-Castillo; Jesús A. Caamal-Maldonado; Pablo J. Ramírez-Barajas; William R. Cetzal-Ix; Héctor Estrada-Medina (Agriculture, Ecosystems & Environment, 2023)

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

The dynamics of arsenic and copper in solid and aqueous phases in reactive confluences receiving acid drainage: The role of turbidity and particle size - J.A. Díaz; D. Castillo; R. Oyarzún; A. Briso; M. Montecinos; P. Pastén (Environmental Pollution, 2023)

Prioritization of areas for groundwater monitoring using analytic hierarchy process method in Geographic Information Systems: a case of Mexico - J. M. Esquivel-Martínez; J. L. Expósito-Castillo; M. V. Esteller-Alberich; M. A. Gómez-Albores; C. M. Medina-Rivas; C. R. Fonseca-Ortiz (International Journal of Environmental Science and Technology, 2023)

Composites of Co-Al hydrotalcites and carbon nanomaterials for photocatalytic H2 production - Dolores G. Gil-Gavilán; Daniel Cosano; Miguel Castillo-Rodríguez; Gustavo de Miguel; Dolores Esquivel; César Jiménez-Sanchidrián; José R. Ruiz; Francisco J. Romero-Salguero (Applied Clay Science, 2023)

The removal of dissolved organic matter by marine sponges is a function of its composition and concentration: An in situ seasonal study of four Mediterranean species - M. Ribes; G. Yahel; C. Romera-Castillo; R. Mallenco; T.M. Morganti; R. Coma (Science of The Total Environment, 2023)

Surface wind strength and sea surface temperature connections along the south peruvian coast during the last 150 years - F. Briceño-Zuluaga; V. Flores-Aqueveque; J. Nogueira; A. Castillo; J. Cardich; J. Rutllant; S. Caquineau; A. Sifeddine; R. Salvatteci; J. Valdes; D. Gutierrez (Aeolian Research, 2023)

An Analysis of Policy Options Available to the International Maritime Organization to Protect the Costa Rica Thermal Dome: Building the Case for a Particularly Sensitive Sea Area - Richard Castillo Rodríguez; Jorge Jiménez; Katherine Arroyo Arce; Katie R. Thompson (Marine Policy, 2023)

Aerosolized aqueous dust extracts collected near a drying lake trigger acute neutrophilic pulmonary inflammation reminiscent of microbial innate immune ligands - Trevor A. Biddle; Keziyah Yisrael; Ryan Drover; Qi Li; Mia R. Maltz; Talyssa M. Topacio; Jasmine Yu; Diana Del Castillo; Daniel Gonzales; Hannah L. Freund; Mark P. Swenson; Malia L. Shapiro; et al. (Science of The Total Environment, 2023)

Molecular markers for thermo-tolerance are associated with reproductive and physiological traits in Pelibuey ewes raised in a semiarid environment - Candelario A. Castillo-Salas; Guillermo Luna-Nevárez; Javier R. Reyna-Granados; Rosa I. Luna-Ramirez; Sean W. Limesand; Pablo Luna-Nevárez (Journal of Thermal Biology, 2023)

Lactoferrin gene polymorphisms associated with clinical mastitis in Honduran Holstein inheritance cows - M. Moncada-Laínez; P. A. Valladares-Medina; R. Castillo; X. F. De la Rosa-Reyna; A. M. Sifuentes-Rincón; V. R. Moreno-Medina; A. L. Lara-Rivera; G. M. Parra-Bracamonte (Molecular Biology Reports, 2023)

A review of estimation methods for natural mortality and their performance in the context of fishery stock assessment - Mark N. Maunder; Owen S. Hamel; Hui-Hua Lee; Kevin R. Piner; Jason M. Cope; André E. Punt; James N. Ianelli; Claudio Castillo-Jordán; Maia S. Kapur; Richard D. Methot (Fisheries Research, 2023)

Effect of bovine oocyte vitrification with EGTA and post-warming recovery with resveratrol on meiotic spindle, mitochondrial function, reactive oxygen species, and developmental competence - Emilio Gutierrez-Castillo; Fabian A. Diaz; Sydney A. Talbot; Kenneth R. Bondioli (Theriogenology, 2023)

Refuelling infrastructure requirements for renewable hydrogen road fuel through the energy transition - John M. Low; R. Stuart Haszeldine; Julien Mouli-Castillo (Energy Policy, 2023)

Palaeozoic – Early Mesozoic geological history of the Antarctic Peninsula and correlations with Patagonia: Kinematic reconstructions of the proto-Pacific margin of Gondwana - Teal R. Riley; Alex Burton-Johnson; Michael J. Flowerdew; Fernando Poblete; Paula Castillo; Francisco Hervé; Philip T. Leat; Ian L. Millar; Joaquin Bastias; Martin J. Whitehouse (Earth-Science Reviews, 2023)

Nitrogen and phosphorus budget in an intensive irrigation area and effects on littoral water and groundwater (Yaqui Valley, Northwestern Mexico) - B. R. Almazán; M. V. Esteller; S. E. Garrido-Hoyos; J. L. Expósito-Castillo; C. Díaz-Delgado; J. C. García-Colín (Environmental Monitoring and Assessment, 2023)

Inconsistent response of taxonomic groups to space and environment in mediterranean and tropical pond metacommunities - Ángel Gálvez; Pedro R. Peres‐Neto; Andreu Castillo‐Escrivà; Fabián Bonilla; Antonio Camacho; Eduardo M. García‐Roger; Sanda Iepure; Javier Miralles‐Lorenzo; Juan S. Monrós; Carla Olmo; Antonio Picazo; Carmen Rojo; et al. (Ecology, 2023)
The metacommunity concept provides a theoretical framework that aims at explaining organism distributions by a combination of environmental filtering, dispersal, and drift. However, few works have attempted a multitaxon approach and even fewer have compared two distant biogeographical regions using the same methodology. We tested the expectation that temperate (mediterranean‐climate) pond metacommunities would be more influenced by environmental and spatial processes than tropical ones, because of stronger environmental gradients and a greater isolation of waterbodies. However, the pattern should be different among groups of organisms depending on their dispersal abilities. We surveyed 30 tropical and 32 mediterranean temporary ponds from Costa Rica and Spain, respectively, and obtained data on 49 environmental variables. We characterized the biological communities of bacteria and archaea (from the water column and the sediments), phytoplankton, zooplankton, benthic invertebrates, amphibians and birds, and estimated the relative role of space and environment on metacommunity organization for each group and region, by means of variation partitioning using generalized additive models. Purely environmental effects were important in both tropical and mediterranean ponds, but stronger in the latter, probably due to their larger limnological heterogeneity. Spatially correlated environment and pure spatial effects were greater in the tropics, related to higher climatic heterogeneity and dispersal processes (e.g., restriction, surplus) acting at different scales. The variability between taxonomic groups in the contribution of spatial and environmental factors to metacommunity variation was very wide, but higher in active, compared with passive, dispersers. Higher environmental effects were observed in mediterranean passive dispersers, and higher spatial effects in tropical passive dispersers. The unexplained variation was larger in the tropical setting, suggesting a higher role for stochastic processes, unmeasured environmental factors, or biotic interactions in the tropics, although this difference affected some actively dispersing groups (insects and birds) more than passive dispersers. These results, despite our limitations in comparing only two regions, provide support, for a wide variety of aquatic organisms, for the classic view of stronger abiotic niche constraints in temperate areas compared with the tropics. The heterogeneous response of taxonomic groups between regions also points to a stronger influence of regional context than organism adaptations on metacommunity organization.

Molecular insights into the invasion dynamics of Carcinus crabs in South Africa - Clova A. Mabin; Tamara B. Robinson; John R. U. Wilson; Heidi Hirsch; Maria L. Castillo; Michelle Jooste; Johannes J. Le Roux (Biological Invasions, 2022)
Knowledge of the introduction history and spread dynamics of invasive species can provide important insights for management (Ens et al. in Environ Rev (in press), 2022), however such information is often unavailable for accidental introductions. Here we infer how the European shore crab, Carcinus maenas , and its congener, the Mediterranean shore crab, C. aestuarii , were introduced to and spread within South Africa. We do this using nuclear microsatellite data and Bayesian assignment tests and Approximate Bayesian Computation (ABC) modelling that included samples from the native and other invasive ranges of these two species. We also compared the genetic diversity and structure of one of the South African populations during and after intensive management, with that of another, unmanaged, population. South African populations had higher genetic diversity than invasive Carcinus populations from elsewhere in the world. Moreover, the ABC analyses suggest that South African populations originated from an admixture event between individuals of C. maenas from a population in the native range and an invasive population from Canada. We also identified instances of hybridisation between Carcinus maenas and C. aestuarii in South Africa. South African populations showed no genetic structure, suggesting either extensive migration between them or that populations arose from the same initial introduction. Management of Carcinus did not affect genetic diversity or structure, and we suspect that the management duration was insufficient to target a full generation of crabs. Together these results suggest multiple introductions and/or high propagule pressure to South Africa, crab (larval or adult) movement between existing populations, and some hybridisation. For eradication from South Africa to be achieved, management would need to concurrently target all known invasive populations and clearly establish that new introductions could be prevented.

Title: Present status and management of coastal lagoons in the Sabana–Camagüey Archipelago I: environmental baseline at lagoons of Cayo Sabinal - R. González-De; Zayas; M. Merino-Ibarra; J. A. Lestayo González; F. S Castillo – Sandoval (Thalassas: An International Journal of Marine Sciences, 2022)

Aridification‐driven evolution of a migratory fish revealed by niche modelling and coalescence simulations - Emily J. Booth; Jonathan Sandoval‐Castillo; Catherine R. M. Attard; Dean M. Gilligan; Peter J. Unmack; Luciano B. Beheregaray (Journal of Biogeography, 2022)
Aim Major knowledge gaps exist regarding the evolution of arid zone organisms. For freshwater species with high dispersal potential, little is known if historical aridification influenced connectivity across drainage divides and impacted on their divergence and diversification. We tested the hypothesis that the historical aridification of Australia promoted the isolation and influenced the demographic histories and evolutionary divergence of a migratory group of freshwater obligates. Location Central and eastern Australia; Murray–Darling Basin (MDB), Lake Eyre Basin (LEB), Fitzroy Basin (FIT). Taxon Three lineages of golden perch ( Macquaria ambigua ), a widespread fishery resource from inland Australia. Methods We obtained genome‐wide data for golden perch sampled throughout their range. Phylogenetic relationships were reconstructed using maximum likelihood. Species distribution modelling was used to predict contemporary and past distributions for the three lineages and to develop hypotheses regarding their biogeographic and demographic histories. Hypotheses were independently tested using coalescent simulations in fastsimcoal and DIYABC with the genomic dataset. Results We found evidence for three reciprocally monophyletic lineages that have experienced little to nil genetic connectivity since divergence. Coalescent models suggest that the coastal (FIT) and inland (MDB and LEB) lineages diverged ~103 thousand years ago (ka), followed by the split of MDB and LEB lineages ~58 ka. These timings agree with reductions of large freshwater environments in Australia during the late Pleistocene. Species distribution models show an extreme decrease in habitat during the Last Glacial Maximum ~21 ka, consistent with inferred demographic contractions in coalescent tests. Main conclusions We reveal that aridification of Australia during the late Pleistocene has driven and reinforced the divergence of a migratory freshwater obligate. Our findings are important for informing the conservation management of aquatic organisms under climate change. This work further demonstrates the value of using species distribution modelling to formulate diversification hypotheses and to improve interpretation of coalescent analyses.

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

DNA barcoding of Glossogobius species (Teleostei: Gobiidae) from major lakes in the Philippines reveals the presence of cryptic species and species complexes - Onaya P. Abdulmalik-Labe; Nicole Mae R. Picart; Mirriam Esther M. Francisco; Raisa Mikaelle G. Castillo; Jonas P. Quilang (Conservation Genetics Resources, 2022)

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Correction to: A study on correlations between precipitation ETCCDI and airborne pollen/fungal spore parameters in the NE Iberian Peninsula - R. Rodríguez-Solà; M. C. Casas-Castillo; J. J. Ho Zhang; R. Kirchner; M. Alarcón; C. Periago; C. De Linares; J. Belmonte (International Journal of Biometeorology, 2022)

A study on correlations between precipitation ETCCDI and airborne pollen/fungal spore parameters in the NE Iberian Peninsula - R. Rodríguez-Solà; M. C. Casas-Castillo; J. J. Ho Zhang; R. Kirchner; M. Alarcón; C. Periago; C. De Linares; J. Belmonte (International Journal of Biometeorology, 2022)

Mapping the Cerebellar Cognitive Affective Syndrome in Patients with Chronic Cerebellar Strokes - Amanda Chirino-Pérez; Oscar René Marrufo-Meléndez; José Ignacio Muñoz-López; Carlos R. Hernandez-Castillo; Gabriel Ramirez-Garcia; Rosalinda Díaz; Lilia Nuñez-Orozco; Juan Fernandez-Ruiz (The Cerebellum, 2022)

Genomics outperforms genetics to manage mistakes in fisheries stocking of threatened species - Catherine R. M. Attard; Jonathan Sandoval-Castillo; Dean M. Gilligan; Peter J. Unmack; Leanne K. Faulks; Luciano B. Beheregaray (Biodiversity and Conservation, 2022)
Hatchery production and fisheries stocking is a widespread and high profile management practice because it allows recreational fisheries to continue in threatened species. Human-mediated transfer of fish across the geographic boundaries of intraspecies lineages or closely related species can cause introgression and occasionally outbreeding depression. Hybridization can be difficult to detect due to limited morphological differences among close lineages and the relatively low power of traditional genetic datasets. Here we showcase the use of genomic techniques to detect admixture of the economically important and threatened golden perch ( Macquaria ambigua ) in the Murray-Darling Basin, southeast Australia. We detected admixture through a genome-wide dataset of 6,862 single nucleotide polymorphisms (SNPs) across 174 Murray-Darling sourced fish and 15 fish from each of two neighbouring basins: the Lake Eyre and Fitzroy basins. Individuals with partial ancestry from both neighboring basins were detected using genomics throughout the Murray-Darling, suggesting the release of individuals and introgression into the Murray-Darling Basin. Importantly, a traditional microsatellite dataset was unreliable for identifying admixed individuals. The SNP-detected admixed individuals were also found in Murray-Darling impoundments, where fish are solely sourced from government-managed hatcheries, suggesting that some broodstock in hatcheries might have non-endemic ancestry. Stocking programs for golden perch release over one million fingerlings each year, and so could impact the genetic variation in the wild. We advocate for using genomics to check the ancestry of broodstock and for increasing collaboration between managers and academics—as done here—to better integrate the power of genomics into biodiversity management and conservation.

Small Differences in Diet Facilitate the Coexistence of Three Forage Fish Species in an Inshore Northern Patagonian Habitat - Lauren E. Wiesebron; Leonardo R. Castro; Samuel Soto; Jorge Castillo (Frontiers in Marine Science, 2022)
Forage fish play the crucial role of transferring energy from lower to upper trophic levels. These small pelagic fish feed on plankton and can compete with each other for food, leading to potentially complex interactions. Three forage fish species ( Sprattus fuegensis , Strangomera bentincki , and Engraulis ringens ) are commonly found in the inshore waters of Northern Chilean Patagonia, a region with large spatial variability in oceanographic conditions and in the zooplankton community. To better understand what factors may explain coexistence among these three forage fish species, we examined differences in resource availability (zooplankton community and abundances) in three locations (Chiloé, Cordillera, and Aysén regions) within Northern Patagonia. We compared the diet of the three fish species using both stable isotope and stomach content analyses, and we measured their gill rakers. S. fuegensis , the only species found in all three regions, had flexible diets which lent it greater success than the other two species at foraging in waters with fewer prey. We found little diet differentiation among the three species in the copepod-rich Cordillera region, but the diverging diets of S. bentincki and S. fuegensis in the copepod-poor Chiloé region suggest that diet partitioning in areas with fewer resources is due to competition. The small differences in diet facilitates coexistence among the three species, which may help explain the lack of correlation between the three species’ population abundances in the Cordillera region over the past 6 years. Finally, our results show that the high degree of oceanographic heterogeneity in Northern Patagonia may encourage species separation based on their specific environmental requirements.

Stable inversion clines in a grasshopper species group despite complex geographical history - Noelia V. Guzmán; Petri Kemppainen; Daniela Monti; Elio R. D. Castillo; Marcela S. Rodriguero; Andrés F. Sánchez‐Restrepo; Maria Marta Cigliano; Viviana A. Confalonieri (Molecular Ecology, 2022)
Chromosomal inversions are known to play roles in adaptation and differentiation in many species. They involve clusters of correlated genes (i.e., loci in linkage disequilibrium, LD) possibly associated with environmental variables. The grasshopper “species complex” Trimerotropis pallidipennis comprises several genetic lineages distributed from North to South America in arid and semi‐arid high‐altitude environments. The southernmost lineage, Trimerotropis sp., segregates for four to seven putative inversions that display clinal variation, possibly through adaptation to temperate environments. We analysed chromosomal, mitochondrial and genome‐wide single nucleotide polymorphism data in 19 Trimerotropis sp. populations mainly distributed along two altitudinal gradients (MS and Ju). Populations across Argentina comprise two main chromosomally and genetically differentiated lineages: one distributed across the southernmost border of the “Andes Centrales,” adding evidence for a differentiation hotspot in this area; and the other widely distributed in Argentina. Within the latter, network analytical approaches to LD found three clusters of correlated loci (LD‐clusters), with inversion karyotypes explaining >79% of the genetic variation. Outlier loci associated with environmental variables mapped to two of these LD‐clusters. Furthermore, despite the complex geographical history indicated by population genetic analyses, the clines in inversion karyotypes have remained stable for more than 20 generations, implicating their role in adaptation and differentiation within this lineage. We hypothesize that these clines could be the consequence of a coupling between extrinsic postzygotic barriers and spatially varying selection along environmental gradients resulting in a hybrid zone. These results provide a framework for future investigations about candidate genes implicated in rapid adaptation to new environments.

Cerebellar Degeneration Signature in Huntington’s Disease - Gustavo Padron-Rivera; Rosalinda Diaz; Israel Vaca-Palomares; Adriana Ochoa; Carlos R. Hernandez-Castillo; Juan Fernandez-Ruiz (The Cerebellum, 2021)

Ecological Drawbacks of Nanomaterials Produced on an Industrial Scale: Collateral Effect on Human and Environmental Health - H. Pérez-Hernández; A. Pérez-Moreno; C. R. Sarabia-Castillo; S. García-Mayagoitia; G. Medina-Pérez; F. López-Valdez; R. G. Campos-Montiel; P. Jayanta-Kumar; F. Fernández-Luqueño (Water, Air, & Soil Pollution, 2021)

Probiotic Properties of Alcaligenes faecalis Isolated from Argyrosomus regius in Experimental Peritonitis (Rat Model) - A. I. Gutiérrez-Falcón; A. M. Ramos-Nuez; A. Espinosa de los Monteros y Zayas; D. F. Padilla Castillo; M. Isabel García-Laorden; F. J. Chamizo-López; F. Real Valcárcel; F. Artilles Campelo; A. Bordes Benítez; P. Nogueira Salgueiro; C. Domínguez Cabrera; J. C. Rivero-Vera; et al. (Probiotics and Antimicrobial Proteins, 2021)
A strain of Alcaligenes faecalis A12C ( A. faecalis A12C) isolated from Argyrosomus regius is a probiotic in fish. Previous experiments showed that A. faecalis A12C had inhibitory effects on the growth of multidrug-resistant bacteria. We aimed to confirm whether A. faecalis A12C is safe and has adequate intestinal colonization in experimental rats, and evaluate its efficacy in an animal model of peritonitis . We used 30 male rats, randomly divided into 6 groups ( n = 5): three groups (HA7, HA15, HA30) received A. faecalis A12C in drinking water (6 × 10 8 CFU/mL) for 7 days, and three control groups received drinking water only. All groups were evaluated at 7, 15, and 30 days. Survival after A. faecalis A12C administration was 100% in all groups. Mild eosinophilia (1.5%, p < 0.01) and increased aspartate aminotransferase (86 IU/L, p < 0.05) were observed in HA7, followed by progressive normalization. No histological signs of organ injury were found. We observed significant E. coli decline in faeces, parallel to an increase in A. faecalis A12C at 7 days. E. coli had a tendency to recover initial values, while A. faecalis A12C disappeared from the intestinal microbiota at 30 days. To evaluate its efficacy against peritonitis, we studied two additional groups of animals: IA group pretreated with A. faecalis A12C before E. coli intra-abdominal inoculation, and IC group inoculated with no A. faecalis A12C. We found an increase in C-reactive protein, alanine aminotransferase, urea, and eosinophils in IC animals when compared with IA. Peritonitis was more evident in IC than in IA animals. Our findings suggest that A. faecalis A12C altered clinically relevant parameters in sepsis and was associated with a lesser spread of infection.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

The effects of three types of exercise training on steroid hormones in physically inactive middle-aged adults: a randomized controlled trial - Manuel Dote-Montero; Alejandro De-la-O; Lucas Jurado-Fasoli; Jonatan R. Ruiz; Manuel J. Castillo; Francisco J. Amaro-Gahete (European Journal of Applied Physiology, 2021)

Secundiflorol G isolated from Aeschynomene fascicularis , a Mayan medicinal plant, induces apoptosis in cervical cancer cells - Cristina M. Castillo-Bautista; Luis W. Torres-Tapia; Alfredo Lagunas-Martínez; Carla O. Contreras-Ochoa; Sergio R. Peraza-Sanchez; Rosa Moo-Puc (Natural Product Research, 2021)

A Matter of Scale: Population Genomic Structure and Connectivity of Fisheries At-Risk Common Dolphins (Delphinus delphis) From Australasia - Andrea Barceló; Jonathan Sandoval-Castillo; Karen A. Stockin; Kerstin Bilgmann; Catherine R. M. Attard; Nikki Zanardo; Guido J. Parra; Krista Hupman; Isabella M. Reeves; Emma L. Betty; Gabriela Tezanos-Pinto; Luciano B. Beheregaray; et al. (Frontiers in Marine Science, 2021)
An understanding of population structure and connectivity at multiple spatial scales is required to assist wildlife conservation and management. This is particularly critical for widely distributed and highly mobile marine mammals subject to fisheries by-catch. Here, we present a population genomic assessment of a near-top predator, the common dolphin ( Delphinus delphis ), which is incidentally caught in multiple fisheries across the Australasian region. The study was carried out using 14,799 ddRAD sequenced genome-wide markers genotyped for 478 individuals sampled at multiple spatial scales across Australasia. A complex hierarchical metapopulation structure was identified, with three highly distinct and genetically diverse regional populations at large spatial scales (>1,500 km). The populations inhabit the southern coast of Australia, the eastern coast of Australia, New Zealand, and Tasmania, with the latter also showing a considerable level of admixture to Australia's east coast. Each of these regional populations contained two to four nested local populations (i.e., subpopulations) at finer spatial scales, with most of the gene flow occurring within distances of 50 to 400 km. Estimates of contemporary migration rates between adjacent subpopulations ranged from 6 to 25%. Overall, our findings identified complex common dolphin population structure and connectivity across state and international jurisdictions, including migration and gene flow across the Tasman Sea. The results indicate that inter-jurisdictional collaboration is required to implement conservation management strategies and mitigate fisheries interactions of common dolphins across multiple spatial scales in the Australasian region.

Pseudacanthus alani, a New Species of Mesoamerican Bess Beetles (Coleoptera: Passalidae) of Oaxaca, Mexico and Nomenclatural Notes for the Genus - E R Ariza-Marín; L Jiménez-Ferbans; P Reyes-Castillo (Neotropical Entomology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Characterization of standardized heavy rainfall profiles for Barcelona city: clustering, rain amounts and intensity peaks - X. Lana; R. Rodríguez-Solà; M. D. Martínez; M. C. Casas-Castillo; C. Serra; A. Burgueño (Theoretical and Applied Climatology, 2020)

Diffusible and volatile organic compounds produced by avocado rhizobacteria exhibit antifungal effects against Fusarium kuroshium - Edgar Guevara-Avendaño; Karla R. Bravo-Castillo; Juan L. Monribot-Villanueva; Ana L. Kiel-Martínez; Mónica Ramírez-Vázquez; José A. Guerrero-Analco; Frédérique Reverchon (Brazilian Journal of Microbiology, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Nutritional factors modulating plant and fruit susceptibility to pathogens: BARD workshop, Haifa, Israel, February 25–26, 2018 - Dov Prusky; Leandro José de Assis; Riccardo Baroncelli; Ernesto P. Benito; Virginia Casado del Castillo; Timothy Chaya; Shay Covo; José María Díaz-Mínguez; Nicole M. Donofrio; Eduardo Espeso; Tânia Ribeiro Fernandes; Gustavo H. Goldman; et al. (Phytoparasitica, 2020)

A New Species of Moth Lacewing from the Mesoamerican Genus Adamsiana Penny 1996 (Neuroptera: Ithonidae) - A. Ardila-Camacho; R. Castillo-Argaez; J. I. Martínez (Neotropical Entomology, 2020)

Could Alternaria solani IA300 be a plant growth-promoting fungus? - Jorge A. Mauricio-Castillo; Silvia Salas-Muñoz; Luis R. Reveles-Torres; Miguel A. Salas-Luevano; Fatima B. Salazar-Badillo (European Journal of Plant Pathology, 2020)

A morphological, reproductive, and molt phenology database for 379 bird species from the Colombian Tropical Andes - Leydy J. Cardona‐Salazar; Yeny A. Benavides‐Ossa; Ángela M. Vargas‐Daza; Juan F. Betancurt‐Grisales; Mauricio Bohada‐Murillo; Estefani T. Martínez‐Sánchez; Marelid Cardona‐Romero; Ana Busi; William D. Tobón‐Escobar; Mateo Ortíz‐Giraldo; Daniela Gómez Castillo; Johnathan Alvarez‐Londoño; et al. (Ecology, 2020)
The Colombian Tropical Andes are one of the regions with highest bird diversity on Earth. However, information on bird morphology, reproductive phenology, and molt is particularly scarce in this region. Also, this region is heavily impacted by deforestation, and it is vulnerable to climate change. Hence, providing baseline information on life history and morphological traits will be essential to support future research on functional diversity, climate change effects, conservation, evolution, and phenology. To fill this gap, we have compiled information on bird distribution, morphology, molt, and reproductive phenology at 52 localities of the Department of Caldas, covering an elevation range between 148 and 3845 m. This compilation comprises a wide range of habitats, including native forests, forestry plantations, croplands, and paramo. Our database presents information for 3,398 records belonging to 379 bird species (representing 23 orders, 53 families, and 258 genera). From those records, 2,843 correspond to information collected in the field between 2008 and 2019, and the remaining 555 records correspond to specimens deposited in the Natural History Museum of the Caldas University, collected between 1969 and 2014. We measured nine morphological traits from all specimens: total culmen, gape, bill width, bill depth, tarsus, wing length, tail length, total length, and mass. We also have reproductive condition information for 257 species and molt information available for 378 species. The information contained in this data set represents ~20% of the Colombian avifauna and ~11% of the bird species richness in South America. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Inorganic and organic characterization of Santa Lucía salt mine peloid for quality evaluations - Nadia Martínez-Villegas; Margaret Suárez Muñoz; Patricia González-Hernández; Clara Melián Rodríguez; Josiel Barrios Cossio; Rebeca Hernández Díaz; Juan R. Fagundo Castillo; Alina Gelen Rudnikas; Cristina Díaz López; Aurora Pérez-Gramatges; Oscar Díaz Rizo (Environmental Science and Pollution Research, 2020)

Update of the population size and breeding performance of gentoo penguins (Pygoscelis papua) at Stranger Point/Cabo Funes, South Shetland Islands - Mariana A. Juáres; Ricardo Casaux; Javier Negrete; Ayelen Rios; Martín Castillo; Néstor R. Coria; Mercedes M. Santos (Polar Biology, 2020)

Clinical isolates of Escherichia coli are resistant both to antibiotics and organotin compounds - M. Aguilar-Santelises; J. Castillo-Vera; R. Gonzalez-Molina; A. Garcia del Valle; M. Cruz Millan; L. Aguilar-Santelises (Folia Microbiologica, 2020)

Growth, forage yield and quality of Morus alba L. and Gliricidia sepium (Jacq.) Walp. in mixed and pure fodder bank systems in Yucatan, México - Olivier S. Ramos-Trejo; Jorge R. Canul-Solís; Azucena del R. Alvarado-Canché; Luis E. Castillo-Sánchez; Juan J. Sandoval-Gío; María J. Campos-Navarrete; Angel T. Piñeiro-Vázquez; Alfonso J. Chay-Canul; Fernando Casanova-Lugo (Agroforestry Systems, 2020)

Nitrogen assimilation in picocyanobacteria inhabiting the oxygen‐deficient waters of the eastern tropical North and South Pacific - Montserrat Aldunate; Carlos Henríquez‐Castillo; Qixing Ji; Jessica Lueders‐Dumont; Margaret R. Mulholland; Bess B. Ward; Peter von Dassow; Osvaldo Ulloa (Limnology and Oceanography, 2020)
Prochlorococcus and Synechococcus are the most abundant free‐living photosynthetic microorganisms in the ocean. Uncultivated lineages of these picocyanobacteria also thrive in the dimly illuminated upper part of oxygen‐deficient zones (ODZs), where an important portion of ocean nitrogen (N) loss takes place via denitrification and anaerobic ammonium oxidation. Recent metagenomic studies revealed that ODZ Prochlorococcus have the genetic potential for using different N forms, including nitrate and nitrite, uncommon N sources for Prochlorococcus , but common for Synechococcus . To determine which N sources ODZ picocyanobacteria are actually using in nature, the cellular 15 N natural abundance (δ 15 N) and assimilation rates of different N compounds were determined using cell sorting by flow cytometry and mass spectrometry. The natural δ 15 N of the ODZ Prochlorococcus varied from −4.0‰ to 13.0‰ ( n = 9), with 50% of the values in the range of −2.1–2.6‰. While the highest values suggest nitrate use, most observations indicate the use of nitrite, ammonium, or a mixture of N sources. Meanwhile, incubation experiments revealed potential assimilation rates of ammonium and urea in the same order of magnitude as that expected for total N in several environments including ODZs, whereas rates of nitrite and nitrate assimilation were very low. Our results thus indicate that reduced forms of N and nitrite are the dominant sources for ODZ picocyanobacteria, although nitrate might be important on some occasions. ODZ picocyanobacteria might thus represent potential competitors with anammox bacteria for ammonium and nitrite, with ammonia‐oxidizing archaea for ammonium, and with nitrite‐oxidizing bacteria for nitrite.

The effects of commonly used anaesthetics on colour measurements across body regions in the poeciliid fish, Girardinus metallicus - Erin M. Wojan; Nalana C. Carreiro; David A. Clendenen; Heather M. Neldner; Crystal Castillo; Susan M. Bertram; Gita R. Kolluru (Journal of Fish Biology, 2019)
The effects of common anaesthetics on the hue, saturation and brightness measurements of the poeciliid fish Girardinus metallicus were investigated in two experiments. For both experiments the coloration of four body regions was measured from digital images of the same males obtained under three conditions: (1) control (in a water‐filled chamber); (2) anaesthetised with MS‐222; and (3) anaesthetised with eugenol (clove oil). In experiment 1 anaesthetised fish were photographed out of water. In experiment 2 all photographs were taken in a water‐filled chamber. Anaesthetics altered coloration in both experiments. In the more methodologically consistent experiment 2 we found significantly different hue, increased saturation and decreased brightness in anaesthetic v . control conditions, consistent with darkening caused by the anaesthetics. The body regions differed in coloration consistent with countershading but did not differentially change in response to anaesthesia. These findings suggest that photographing fish in a water‐filled chamber without anaesthetic is preferable for obtaining digital images for colour analysis and that multiple body regions of fish should be measured when assessing coloration patterns meaningful in behavioural contexts, to account for the gradients caused by countershading. We are encouraged that some researchers employ such methods already and caution against using anaesthetics except when absolutely necessary for immobilisation.

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Deep reef fishes in the world’s epicenter of marine biodiversity - Hudson T. Pinheiro; Bart Shepherd; Cristina Castillo; Rene A. Abesamis; Joshua M. Copus; Richard L. Pyle; Brian D. Greene; Richard R. Coleman; Robert K. Whitton; Emma Thillainath; Abner A. Bucol; Matthew Birt; et al. (Coral Reefs, 2019)

Recent emergence and extinction of the protection of telomeres 1c gene in Arabidopsis thaliana - Callie R. Kobayashi; Claudia Castillo-González; Yulia Survotseva; Elijah Canal; Andrew D. L. Nelson; Dorothy E. Shippen (Plant Cell Reports, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Can wave coupling improve operational regional ocean forecasts for the north-west European Shelf? - Huw W. Lewis; Juan Manuel Castillo Sanchez; John Siddorn; Robert R. King; Marina Tonani; Andrew Saulter; Peter Sykes; Anne-Christine Pequignet; Graham P. Weedon; Tamzin Palmer; Joanna Staneva; Lucy Bricheno (Ocean Science, 2019)
Operational ocean forecasts are typically produced by modelling systems run using a forced mode approach. The evolution of the ocean state is not directly influenced by surface waves, and the ocean dynamics are driven by an external source of meteorological data which are independent of the ocean state. Model coupling provides one approach to increase the extent to which ocean forecast systems can represent the interactions and feedbacks between ocean, waves, and the atmosphere seen in nature. This paper demonstrates the impact of improving how the effect of waves on the momentum exchange across the ocean–atmosphere interface is represented through ocean–wave coupling on the performance of an operational regional ocean prediction system. This study focuses on the eddy-resolving (1.5 km resolution) Atlantic Margin Model (AMM15) ocean model configuration for the north-west European Shelf (NWS) region. A series of 2-year duration forecast trials of the Copernicus Marine Environment Monitoring Service (CMEMS) north-west European Shelf regional ocean prediction system are analysed. The impact of including ocean–wave feedbacks via dynamic coupling on the simulated ocean is discussed. The main interactions included are the modification of surface stress by wave growth and dissipation, Stokes–Coriolis forcing, and wave-height-dependent ocean surface roughness. Given the relevance to operational forecasting, trials with and without ocean data assimilation are considered. Summary forecast metrics demonstrate that the ocean–wave coupled system is a viable evolution for future operational implementation. When results are considered in more depth, wave coupling was found to result in an annual cycle of relatively warmer winter and cooler summer sea surface temperatures for seasonally stratified regions of the NWS. This is driven by enhanced mixing due to waves, and a deepening of the ocean mixed layer during summer. The impact of wave coupling is shown to be reduced within the mixed layer with assimilation of ocean observations. Evaluation of salinity and ocean currents against profile measurements in the German Bight demonstrates improved simulation with wave coupling relative to control simulations. Further, evidence is provided of improvement to simulation of extremes of sea surface height anomalies relative to coastal tide gauges.

Neuroprotective effect of Mayan medicinal plant extracts against glutamate-induced toxicity - Cristina M. Castillo-Bautista; Luis W. Torres-Tapia; Jorge A. Rangel-Méndez; Sergio R. Peraza-Sánchez; Daniel Cortés; Iván Velasco; Rosa E. Moo-Puc (Journal of Natural Medicines, 2019)

Return period curves for extreme 5-min rainfall amounts at the Barcelona urban network - X. Lana; M. C. Casas-Castillo; C. Serra; R. Rodríguez-Solà; A. Redaño; A. Burgueño; M. D. Martínez (Theoretical and Applied Climatology, 2019)

A New Species of Vindex Kaup (Coleoptera: Scarabaeoidea: Passalidae: Passalinae: Proculini) from Oaxaca, Mexico - E. R. Ariza-Marín; P. Reyes-Castillo; V. Moctezuma; J. L. Sánchez-Huerta (Neotropical Entomology, 2019)

Morphological diversity of Huaya India fruits (Melicoccus oliviformis Kunth) in the Maya Lowlands - Mónica I. Jiménez-Rojas; Jaime Martínez-Castillo; Daniel Potter; Gabriel R. Dzib; Horacio S. Ballina-Gómez; Luis Latournerie-Moreno; Rubén H. Andueza-Noh (Genetic Resources and Crop Evolution, 2019)

Rainfall intensity patterns derived from the urban network of Barcelona (NE Spain) - Xavier Lana; C. Serra; M. C. Casas-Castillo; R. Rodríguez-Solà; A. Redaño; A. Burgueño (Theoretical and Applied Climatology, 2018)

Using unmanned aerial vehicle (UAV) surveys and image analysis in the study of large surface‐associated marine species: a case study on reef sharks Carcharhinus melanopterus shoaling behaviour - Guillaume Rieucau; Jeremy J. Kiszka; Jose Carlos Castillo; Johann Mourier; Kevin M. Boswell; Michael R. Heithaus (Journal of Fish Biology, 2018)
A novel image analysis‐based technique applied to unmanned aerial vehicle (UAV) survey data is described to detect and locate individual free‐ranging sharks within aggregations. The method allows rapid collection of data and quantification of fine‐scale swimming and collective patterns of sharks. We demonstrate the usefulness of this technique in a small‐scale case study exploring the shoaling tendencies of blacktip reef sharks Carcharhinus melanopterus in a large lagoon within Moorea, French Polynesia. Using our approach, we found that C. melanopterus displayed increased alignment with shoal companions when distributed over a sandflat where they are regularly fed for ecotourism purposes as compared with when they shoaled in a deeper adjacent channel. Our case study highlights the potential of a relatively low‐cost method that combines UAV survey data and image analysis to detect differences in shoaling patterns of free‐ranging sharks in shallow habitats. This approach offers an alternative to current techniques commonly used in controlled settings that require time‐consuming post‐processing effort.

Synthesis, antimicrobial activity, and molecular docking study of fluorine-substituted indole-based imidazolines - Humberto L. Mendoza-Figueroa; Maria Trinidad Serrano-Alva; Gerardo Aparicio-Ozores; Gelacio Martínez-Gudiño; Oscar R. Suárez-Castillo; Nadia A. Pérez-Rojas; Martha S. Morales-Ríos (Medicinal Chemistry Research, 2018)

Lower tier toxicity risk assessment of agriculture pesticides detected on the Río Madre de Dios watershed, Costa Rica - M Arias-Andrés; R Rämö; F Mena Torres; R Ugalde; L Grandas; C Ruepert; L E Castillo; P J Van den Brink; J S Gunnarsson (Environmental Science and Pollution Research, 2018)

Areas of endemism persist through time: A palaeoclimatic analysis in the Mexican Transition Zone - Gonzalo E. Pinilla‐Buitrago; Tania Escalante; Ana Gutiérrez‐Velázquez; Pedro Reyes‐Castillo; Octavio R. Rojas‐Soto (Journal of Biogeography, 2018)
Aim The Mexican Transition Zone ( MTZ ) is an area where the Nearctic and Neotropical biogeographical regions overlap, generating high species richness and endemism. The objective of this study was to analyse if potential changes in the composition and the geographical location of areas of endemism (AEs) for beetles and mammals during the Last Glacial Maximum ( LGM ), the mid‐Holocene ( MH ) or the Last Interglacial ( LIG ) have influenced the definition of the MTZ in the present. Location Mexico and Central America. Methods Ecological niche models ( ENM ) were generated describing the current distribution of 218 species associated with the MTZ and then transferred to three periods into the past. A parsimony analysis of endemicity ( PAE ) was run to identify current AE s. The transferred models of each set of species that form the current AE s were used to assess if the geographical ranges of the species’ ecological niches changed over time, or whether they remained stable supporting the validation of the AE s during three past recent periods ( LGM , MH and LIG ). Results Two current AEs were detected that persisted geographically during the three past periods ( LGM , MH and LIG ). Main conclusions The results show that some AEs change through time as a response of climate, whereas others remained stable. Thus, the MTZ could be considered as a dynamic zone at least over the last 130,000 years. The climate analysis of the AEs allows them to be recognized either as true spatio‐temporal units, or as temporarily restricted patterns of co‐distribution resulting from changes in climate over time.

Decoupling between the hand territory and the default mode network after bilateral arm transplantation: four-year follow-up case study - Carlos R. Hernandez-Castillo; Jörn Diedrichsen; Erika Aguilar-Castañeda; Martin Iglesias (Brain Imaging and Behavior, 2018)

Designing connected marine reserves in the face of global warming - Jorge G. Álvarez‐Romero; Adrián Munguía‐Vega; Maria Beger; Maria del Mar Mancha‐Cisneros; Alvin N. Suárez‐Castillo; Georgina G. Gurney; Robert L. Pressey; Leah R. Gerber; Hem Nalini Morzaria‐Luna; Héctor Reyes‐Bonilla; Vanessa M. Adams; Melanie Kolb; et al. (Global Change Biology, 2018)
Marine reserves are widely used to protect species important for conservation and fisheries and to help maintain ecological processes that sustain their populations, including recruitment and dispersal. Achieving these goals requires well‐connected networks of marine reserves that maximize larval connectivity, thus allowing exchanges between populations and recolonization after local disturbances. However, global warming can disrupt connectivity by shortening potential dispersal pathways through changes in larval physiology. These changes can compromise the performance of marine reserve networks, thus requiring adjusting their design to account for ocean warming. To date, empirical approaches to marine prioritization have not considered larval connectivity as affected by global warming. Here, we develop a framework for designing marine reserve networks that integrates graph theory and changes in larval connectivity due to potential reductions in planktonic larval duration ( PLD ) associated with ocean warming, given current socioeconomic constraints. Using the Gulf of California as case study, we assess the benefits and costs of adjusting networks to account for connectivity, with and without ocean warming. We compare reserve networks designed to achieve representation of species and ecosystems with networks designed to also maximize connectivity under current and future ocean‐warming scenarios. Our results indicate that current larval connectivity could be reduced significantly under ocean warming because of shortened PLD s. Given the potential changes in connectivity, we show that our graph‐theoretical approach based on centrality (eigenvector and distance‐weighted fragmentation) of habitat patches can help design better‐connected marine reserve networks for the future with equivalent costs. We found that maintaining dispersal connectivity incidentally through representation‐only reserve design is unlikely, particularly in regions with strong asymmetric patterns of dispersal connectivity. Our results support previous studies suggesting that, given potential reductions in PLD due to ocean warming, future marine reserve networks would require more and/or larger reserves in closer proximity to maintain larval connectivity.

Ecological disturbance influences adaptive divergence despite high gene flow in golden perch ( Macquaria ambigua ): Implications for management and resilience to climate change - Catherine R. M. Attard; Chris J. Brauer; Jonathan Sandoval‐Castillo; Leanne K. Faulks; Peter J. Unmack; Dean M. Gilligan; Luciano B. Beheregaray (Molecular Ecology, 2018)
Populations that are adaptively divergent but maintain high gene flow may have greater resilience to environmental change as gene flow allows the spread of alleles that have already been tested elsewhere. In addition, populations naturally subjected to ecological disturbance may already hold resilience to future environmental change. Confirming this necessitates ecological genomic studies of high dispersal, generalist species. Here we perform one such study on golden perch ( Macquaria ambigua ) in the Murray‐Darling Basin ( MDB ), Australia, using a genome‐wide SNP data set. The MDB spans across arid to wet and temperate to subtropical environments, with low to high ecological disturbance in the form of low to high hydrological variability. We found high gene flow across the basin and three populations with low neutral differentiation. Genotype–environment association analyses detected adaptive divergence predominantly linked to an arid region with highly variable riverine flow, and candidate loci included functions related to fat storage, stress and molecular or tissue repair. The high connectivity of golden perch in the MDB will likely allow locally adaptive traits in its most arid and hydrologically variable environment to spread and be selected in localities that are predicted to become arid and hydrologically variable in future climates. High connectivity in golden perch is likely due to their generalist life history and efforts of fisheries management. Our study adds to growing evidence of adaptation in the face of gene flow and highlights the importance of considering ecological disturbance and adaptive divergence in biodiversity management.

Effects of transgenic expression of Brevibacterium linens methionine gamma lyase (MGL) on accumulation of Tylenchulus semipenetrans and key aminoacid contents in Carrizo citrange - Elenor Castillo; Federico Martinelli; Florence Zakharov-Negre; Susan E. Ebeler; Tom R. Buzo; Michael V. McKenry; Abhaya M. Dandekar (Plant Molecular Biology, 2017)

Extracellular DNA and lipoteichoic acids interact with exopolysaccharides in the extracellular matrix of Streptococcus mutans biofilms - Midian C. Castillo Pedraza; Tatiana F. Novais; Roberta C. Faustoferri; Robert G. Quivey; Anton Terekhov; Bruce R. Hamaker; Marlise I. Klein (Biofouling, 2017)

Isotopic evidence for intersexual foraging variation in northern elephant seals from Baja California, Mexico - Miriam A. Velázquez-Castillo; Fernando R. Elorriaga-Verplancken (Marine Biology, 2017)

Estimation of natural outcrossing rate and genetic diversity in Lima bean (Phaseolus lunatus L. var. lunatus) from Brazil using SSR markers: implications for conservation and breeding - J. S. Penha; A. C. A. Lopes; R. L. F. Gomes; J. B. Pinheiro; J. R. Assunção Filho; E. A. Silvestre; J. P. G. Viana; J. Martínez-Castillo (Genetic Resources and Crop Evolution, 2017)

Predictive score of haematological toxicity in patients treated with linezolid - J. González-Del Castillo; F. J. Candel; R. Manzano-Lorenzo; L. Arias; E. J. García-Lamberechts; F. J. Martín-Sánchez (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

A simulation tool for advanced design and management of collective sprinkler-irrigated areas: a study case - N. Zapata; E. H. El Malki; B. Latorre; J. Gallinat; F. J. Citoler; R. Castillo; E. Playán (Irrigation Science, 2017)

Antimicrobial and hormetic effects of silver nanoparticles on in vitro regeneration of vanilla (Vanilla planifolia Jacks. ex Andrews) using a temporary immersion system - J. L. Spinoso-Castillo; R. A. Chavez-Santoscoy; Nina Bogdanchikova; J. A. Pérez-Sato; V. Morales-Ramos; J. J. Bello-Bello (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Ideal cardiovascular health and liver enzyme levels in European adolescents; the HELENA study - Idoia Labayen; Jonatan R. Ruiz; Inge Huybrechts; Francisco B. Ortega; Manuel Castillo; Michael Sjöstrom; Marcela González-Gross; Yannis Manios; Kurt Widhalm; Anthony Kafatos; Christina Breidenassel; Gerardo Rodríguez; et al. (Journal of Physiology and Biochemistry, 2017)

Variability among strains of Aspergillus section Nigri with capacity to degrade tannic acid isolated from extreme environments - F. Lara-Victoriano; F. Veana; F. D. Hernández-Castillo; C. N. Aguilar; M. H. Reyes-Valdés; R. Rodríguez-Herrera (Archives of Microbiology, 2017)

An overview of Australia's temperate marine phylogeography, with new evidence from high‐dispersal gastropods - Peter R. Teske; Jonathan Sandoval‐Castillo; Jonathan Waters; Luciano B. Beheregaray (Journal of Biogeography, 2017)
Aim We provide an overview of the location and ages of coastal phylogeographical breaks in southern Australian planktonic dispersers, and test the hypothesis that the absence of such breaks in some species is an artefact of insufficient resolution of genetic markers when such breaks evolved comparatively recently. Location Temperate coastal Australia. Methods We generated a large (> 1500 individuals) data set from rapidly evolving microsatellite markers for two codistributed Australian coastal gastropods, and compared it with mitochondrial DNA data. Both study species, the snail Nerita atramentosa and the limpet Siphonaria diemenensis , have long planktonic dispersal phases, and neither taxon exhibits substantial regional genetic structure on the basis of mitochondrial DNA . We tested for the presence of genetic structure by means of AMOVA , Bayesian clustering ( structure ) and iterated realloction ( flock ). Results There was no compelling evidence for the existence of more than one evolutionary lineage in either species. Main conclusions Discrepancies in the phylogeographical structuring of co‐distributed intertidal taxa cannot be attributed to insufficient marker resolution for the two species considered here, and likely reflect a combination of abiotic and biotic factors that include porous dispersal barriers, life history and species age/history. It appears that contemporary oceanography does not explain the presence of phylogeographical breaks, but may serve to maintain breaks that evolved earlier. Deep genetic divergence in some of the previously studied coastal invertebrates suggests that these could be cryptic species, in which case competitive exclusion may play a role in constraining species biogeography.

Assessment of a fisheries legal framework for potential development of an ecosystem approach to fisheries management in large rivers - T. I. Castillo; C. R. M. Baigún; P. G. Minotti (Fisheries Management and Ecology, 2016)
Most small‐scale fisheries of large floodplain rivers are still managed under conventional top‐down regulations that limit the application of an ecosystem approach to fisheries ( EAF ) due to inappropriate legal frameworks. Using the Parana–Paraguay River fisheries (Argentina) as an example, this study examines the extent to which existing provincial legislations can be prepared for the adoption of an EAF . An Ecosystem Fishing Legal Approach ( EFLA ) framework is proposed based on different criteria across an environmental–ecological, fishing, social, economic and institutional template. Policy Component Scores ( PCS ) and an Integrated Policy Legal Index ( IPLI ) were applied to assess the degree of compliance by current provincial legislations to EAF implementation. Cluster analysis was used to recognise the potential for articulating a legal framework at a basin scale. The EFLA framework, which provided an accurate picture of how provinces were poorly prepared to adopt an EAF for the Paraguay–Parana fisheries, and represents a suitable tool that can be adapted and extended to other basins around the world.

Spartina versicolor Fabre: Another case of Spartina trans-Atlantic introduction? - A. Baumel; M. Rousseau-Gueutin; C. Sapienza-Bianchi; A. Gareil; N. Duong; H. Rousseau; O. Coriton; R. Amirouche; S. Sciandrello; B. Duarte; I. Caçador; J. M. Castillo; et al. (Biological Invasions, 2016)

Passipassalus brevicornis n. sp.: a New Passalidae (Coleoptera) from Brazilian Amazonian, with a Key to the Species of Passipassalus Reyes-Castillo & Fonseca - L Jiménez-Ferbans; P Reyes-Castillo; C R V da Fonseca (Neotropical Entomology, 2016)

Testing for functional convergence of temperate rainforest tree assemblages in Chile and New Zealand - CH Lusk; M Jimenez‐Castillo; R Aragón; TA Easdale; L Poorter; LF Hinojosa; NWH Mason (New Zealand Journal of Botany, 2016)
An important tenet of biogeography and comparative ecology is that disjunct assemblages in similar physical environments are functionally more similar to each other than to assemblages from other environments. Temperate rainforests in South America, New Zealand and Australia share certain physiognomic similarities, but we are not aware of any statistical evidence that these disjunct plant assemblages share a distinctive suite of functional traits, or trait combinations. We compiled height, leaf, wood and reproductive traits from the 25 commonest arborescent species at Chilean and New Zealand sites matched for summer rainfall, summer maximum temperatures, and winter minimum temperatures. We then used multivariate tests of trait convergence. Tropical and subtropical assemblages served as out‐groups. PERMANOVA showed convergence of trait centroids at the two temperate sites, where trees on average had denser wood and smaller leaves than trees at the (sub)tropical sites. Principal components analyses carried out separately on each assemblage showed that the Chilean and New Zealand assemblages were also the most similar pair in terms of trait relationships, although New Zealand also shared strong similarities with subtropical Argentina. The main axis of variation in both temperate assemblages ranged from small, short‐lived understorey trees with soft leaves, to emergents with sclerophyllous leaves and fairly dense wood. However, the New Zealand assemblage was much richer in small trees with soft leaves than its Chilean counterpart; possible historical influences on this difference include conditions favouring radiation of small trees during the late Neogene in New Zealand, competition from Chusquea bamboos in Chile and the historical absence of browsing mammals from New Zealand. Environmental filtering has produced similar values of individual traits in Chile and New Zealand, but only partial convergence of functional trait combinations. As far as we know, this is the first study to statistically test whether disjunct tree assemblages on climatically matched sites are more functionally similar to each other than to assemblages from other environments.

Sampling method evaluation and empirical model fitting for count data to estimate densities of Oligonychus perseae (Acari: Tetranychidae) on ‘Hass’ avocado leaves in southern California - Jesús R. Lara; Naseem T. Saremi; Martin J. Castillo; Mark S. Hoddle (Experimental and Applied Acarology, 2016)

Application of a multi-criteria decision model to select of design choices for WWTPs - M. Garrido-Baserba; R. Reif; M. Molinos-Senante; L. Larrea; A. Castillo; M. Verdaguer; M. Poch (Clean Technologies and Environmental Policy, 2016)

Habitat availability and gene flow influence diverging local population trajectories under scenarios of climate change: a place‐based approach - Donelle Schwalm; Clinton W. Epps; Thomas J. Rodhouse; William B. Monahan; Jessica A. Castillo; Chris Ray; Mackenzie R. Jeffress (Global Change Biology, 2016)
Ecological niche theory holds that species distributions are shaped by a large and complex suite of interacting factors. Species distribution models ( SDM s) are increasingly used to describe species’ niches and predict the effects of future environmental change, including climate change. Currently, SDM s often fail to capture the complexity of species’ niches, resulting in predictions that are generally limited to climate‐occupancy interactions. Here, we explore the potential impact of climate change on the American pika using a replicated place‐based approach that incorporates climate, gene flow, habitat configuration, and microhabitat complexity into SDM s. Using contemporary presence–absence data from occupancy surveys, genetic data to infer connectivity between habitat patches, and 21 environmental niche variables, we built separate SDM s for pika populations inhabiting eight US National Park Service units representing the habitat and climatic breadth of the species across the western United States. We then predicted occurrence probability under current (1981–2010) and three future time periods (out to 2100). Occurrence probabilities and the relative importance of predictor variables varied widely among study areas, revealing important local‐scale differences in the realized niche of the American pika. This variation resulted in diverse and – in some cases – highly divergent future potential occupancy patterns for pikas, ranging from complete extirpation in some study areas to stable occupancy patterns in others. Habitat composition and connectivity, which are rarely incorporated in SDM projections, were influential in predicting pika occupancy in all study areas and frequently outranked climate variables. Our findings illustrate the importance of a place‐based approach to species distribution modeling that includes fine‐scale factors when assessing current and future climate impacts on species’ distributions, especially when predictions are intended to manage and conserve species of concern within individual protected areas.

Specific cerebellar and cortical degeneration correlates with ataxia severity in spinocerebellar ataxia type 7 - Carlos R. Hernandez-Castillo; Victor Galvez; Rosalinda Diaz; Juan Fernandez-Ruiz (Brain Imaging and Behavior, 2016)

Antioxidant and toxicological evaluation of a Tamarindus indica L. leaf fluid extract - J.C. Escalona-Arranz; R. Perez-Rosés; J. Rodríguez-Amado; H.J. Morris-Quevedo; L.B. Mwasi; O. Cabrera-Sotomayor; R. Machado-García; O. Fong-Lórez; A. Alfonso-Castillo; E. Puente-Zapata (Natural Product Research, 2016)

Utilizing an Ingestible Biosensor to Assess Real-Time Medication Adherence - Peter R. Chai; Jose Castillo-Mancilla; Eric Buffkin; Chad Darling; Rochelle K. Rosen; Keith J. Horvath; Edwin D. Boudreaux; Gregory K. Robbins; Patricia L. Hibberd; Edward W. Boyer (Journal of Medical Toxicology, 2015)

A Study on the Knowledge, Perception, and Use of Breast Cancer Screening Methods and Quality of Care Among Women from Central Mexico - Andrea B. Cruz-Castillo; María A. Hernández-Valero; Shelly R. Hovick; Martha Elva Campuzano-González; Miguel Angel Karam-Calderón; L. Patricia Bustamante-Montes (Journal of Cancer Education, 2015)

Application of Focused Ultrasound-Assisted Extraction to the Determination of Persistent Organic Pollutants (POPs) in Soil Samples - R. Flores-Ramírez; S. E. Medellín-Garibay; C. G. Castillo; C. A. Ilizaliturri-Hernández; B. A. Zuki-Orozco; L. Batres-Esquivel; F. Díaz-Barriga (Bulletin of Environmental Contamination and Toxicology, 2015)

Management of Perennial Warm-Season Bioenergy Grasses. II. Seasonal Differences in Elephantgrass and Energycane Morphological Characteristics Affect Responses to Harvest Frequency and Timing - Chae-In Na; Lynn E. Sollenberger; John E. Erickson; Kenneth R. Woodard; Miguel S. Castillo; M. Kimberly Mullenix; João M. B. Vendramini; Maria L. Silveira (BioEnergy Research, 2015)

World Squid Fisheries - Alexander I. Arkhipkin; Paul G. K. Rodhouse; Graham J. Pierce; Warwick Sauer; Mitsuo Sakai; Louise Allcock; Juan Arguelles; John R. Bower; Gladis Castillo; Luca Ceriola; Chih-Shin Chen; Xinjun Chen; et al. (Reviews in Fisheries Science & Aquaculture, 2015)

Body Size, Fecundity, and Sexual Size Dimorphism in the Neotropical Cricket Macroanaxipha macilenta (Saussure) (Orthoptera: Gryllidae) - R Cueva del Castillo (Neotropical Entomology, 2015)

The Aluminum Cryo-plate Increases Efficiency of Cryopreservation Protocols for Potato Shoot Tips - Shin-ichi Yamamoto; Wunna; Tariq Rafique; Miriam Valle Arizaga; Kuniaki Fukui; Esmeralda J. Cruz Gutierrez; Carlos R. Castillo Martinez; Kazuo Watanabe; Takao Niino (American Journal of Potato Research, 2015)

Cognitive effects and autonomic responses to transcranial pulsed current stimulation - Leon Morales-Quezada; Camila Cosmo; Sandra Carvalho; Jorge Leite; Laura Castillo-Saavedra; Joanna R. Rozisky; Felipe Fregni (Experimental Brain Research, 2015)

Invasive Populations of Elephantgrass Differ in Morphological and Growth Characteristics from Clones Selected for Biomass Production - Lynn E. Sollenberger; Kenneth R. Woodard; João M. B. Vendramini; John E. Erickson; Kenneth A. Langeland; M. Kimberly Mullenix; Chaein Na; Miguel S. Castillo; Maria Gallo; Christine D. Chase; Yolanda López (BioEnergy Research, 2014)

Improving Environmental and Social Targeting through Adaptive Management in Mexico's Payments for Hydrological Services Program - KATHARINE R. E. SIMS; JENNIFER M. ALIX‐GARCIA; ELIZABETH SHAPIRO‐GARZA; LEAH R. FINE; VOLKER C. RADELOFF; GLEN ARONSON; SELENE CASTILLO; CARLOS RAMIREZ‐REYES; PATRICIA YAÑEZ‐PAGANS (Conservation Biology, 2014)
Natural resource managers are often expected to achieve both environmental protection and economic development even when there are fundamental trade‐offs between these goals. Adaptive management provides a theoretical structure for program administrators to balance social priorities in the presence of trade‐offs and to improve conservation targeting. We used the case of Mexico's federal Payments for Hydrological Services program (PSAH) to illustrate the importance of adaptive management for improving program targeting. We documented adaptive elements of PSAH and corresponding changes in program eligibility and selection criteria. To evaluate whether these changes resulted in enrollment of lands of high environmental and social priority, we compared the environmental and social characteristics of the areas enrolled in the program with the characteristics of all forested areas in Mexico, all areas eligible for the program, and all areas submitted for application to the program. The program successfully enrolled areas of both high ecological and social priority, and over time, adaptive changes in the program's criteria for eligibility and selection led to increased enrollment of land scoring high on both dimensions. Three factors facilitated adaptive management in Mexico and are likely to be generally important for conservation managers: a supportive political environment, including financial backing and encouragement to experiment from the federal government; availability of relatively good social and environmental data; and active participation in the review process by stakeholders and outside evaluators. Mejorando los Objetivos Ambiental y Social Mediante el Manejo Adaptativo en el Programa de Pagos por Servicios Hidrológicos en México

The climate in Zafra from 1750 to 1840: history and description of weather observations - M. I. Fernández-Fernández; M. C. Gallego; F. Domínguez-Castro; R. M. Trigo; J. A. García; J. M. Vaquero; J. M. Moreno González; J. Castillo Durán (Climatic Change, 2014)

A novel begomovirus isolated from sida contains putative cis- and trans-acting replication specificity determinants that have evolved independently in several geographical lineages - J. A. Mauricio-Castillo; S. I. Torres-Herrera; Y. Cárdenas-Conejo; G. Pastor-Palacios; J. Méndez-Lozano; G. R. Argüello-Astorga (Archives of Virology, 2014)

Partial characterisation of digestive proteases of the Mayan cichlid Cichlasoma urophthalmus - C. A. Cuenca-Soria; C. A. Álvarez-González; J. L. Ortiz-Galindo; H. Nolasco-Soria; D. Tovar-Ramírez; R. Guerrero-Zárate; A. Castillo-Domínguez; M. A. Perera-García; R. Hernández-Gómez; E. Gisbert (Fish Physiology and Biochemistry, 2014)

Prospecting metal-resistant plant-growth promoting rhizobacteria for rhizoremediation of metal contaminated estuaries using Spartina densiflora - L. Andrades-Moreno; I. del Castillo; R. Parra; B. Doukkali; S. Redondo-Gómez; P. Pérez-Palacios; M. A. Caviedes; E. Pajuelo; I. D. Rodríguez-Llorente (Environmental Science and Pollution Research, 2014)

Changes in gene expression patterns associated with microspore embryogenesis in hexaploid triticale (×Triticosecale Wittm.) - I. Żur; E. Dubas; M. Krzewska; R. A. Sánchez-Díaz; A. M. Castillo; M. P. Vallés (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Landscape effects on gene flow for a climate‐sensitive montane species, the A merican pika - Jessica A. Castillo; Clinton W. Epps; Anne R. Davis; Samuel A. Cushman (Molecular Ecology, 2014)
Climate change is arguably the greatest challenge to conservation of our time. Most vulnerability assessments rely on past and current species distributions to predict future persistence but ignore species' abilities to disperse through landscapes, which may be particularly important in fragmented habitats and crucial for long‐term persistence in changing environments. Landscape genetic approaches explore the interactions between landscape features and gene flow and can clarify how organisms move among suitable habitats, but have suffered from methodological uncertainties. We used a landscape genetic approach to determine how landscape and climate‐related features influence gene flow for A merican pikas ( O chotona princeps ) in C rater Lake National Park. Pikas are heat intolerant and restricted to cool microclimates; thus, range contractions have been predicted as climate changes. We evaluated the correlation between landscape variables and genetic distance using partial Mantel tests in a causal modelling framework, and used spatially explicit simulations to evaluate methods of model optimization including a novel approach based on relative support and reciprocal causal modelling. We found that gene flow was primarily restricted by topographic relief, water and west‐facing aspects, suggesting that physical restrictions related to small body size and mode of locomotion, as well as exposure to relatively high temperatures, limit pika dispersal in this alpine habitat. Our model optimization successfully identified landscape features influencing resistance in the simulated data for this landscape, but underestimated the magnitude of resistance. This is the first landscape genetic study to address the fundamental question of what limits dispersal and gene flow in the A merican pika.

Stomach contents of cetaceans in the Alboran Sea and Gulf of Cadiz. - Garcia-Polo M.; Gimenez Joan; Mons J. Luis; Castillo Juan Jos; De Stephanis R; Santos M.B.; Fernndez Maldonado Carolina (Frontiers in Marine Science, 2014)

Biogeochemical responses to nutrient inputs in a Cuban coastal lagoon: runoff, anthropogenic, and groundwater sources - R. González-De Zayas; M. Merino-Ibarra; M. F. Soto-Jiménez; F. S. Castillo-Sandoval (Environmental Monitoring and Assessment, 2013)

Multiple domestications of the Mesoamerican gene pool of lima bean (Phaseolus lunatus L.): evidence from chloroplast DNA sequences - R. H. Andueza-Noh; M. L. Serrano-Serrano; M. I. Chacón Sánchez; I. Sanchéz del Pino; L. Camacho-Pérez; J. Coello-Coello; J. Mijangos Cortes; D. G. Debouck; J. Martínez-Castillo (Genetic Resources and Crop Evolution, 2013)

Association between individual genetic diversity of two oak host species and canopy arthropod community structure - E. Tovar-Sánchez; L. Valencia-Cuevas; E. Castillo-Mendoza; P. Mussali-Galante; R. V. Pérez-Ruiz; A. Mendoza (European Journal of Forest Research, 2013)

Geochemistry of basaltic lavas from the southern Lau Basin: input of compositionally variable subduction components - Quanshu Yan; Paterno R. Castillo; Xuefa Shi (International Geology Review, 2012)

The Mexican Sugarcane Industry: Overview, Constraints, Current Status and Long-Term Trends - N. Aguilar-Rivera; D. A. Rodríguez L.; V. Enríquez R.; A. Castillo M.; A. Herrera S. (Sugar Tech, 2012)

Time to positivity of blood culture association with clinical presentation, prognosis and ESBL-production in Escherichia coli bacteremia - R. Álvarez; L. Viñas-Castillo; J. A. Lepe-Jiménez; E. García-Cabrera; J. M. Cisneros-Herreros (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A new strain of tomato severe leaf curl virus and a unique variant of tomato yellow leaf curl virus from Mexico - B. Bañuelos-Hernández; J. A. Mauricio-Castillo; Y. Cardenas-Conejo; R. G. Guevara-González; G. R. Arguello-Astorga (Archives of Virology, 2012)

Sensory changes related to breeding for plant architecture and resistance to viruses and anthracnose in bean market class Fabada (Phaseolus vulgaris L.) - J. J. Ferreira; Romero R. del Castillo; E. Perez-Vega; M. Plans; J. Simó; F. Casañas (Euphytica, 2012)

Palm use and social values in rural communities on the coastal plains of Veracruz, Mexico - R. M. González-Marín; P. Moreno-Casasola; R. Orellana; A. Castillo (Environment, Development and Sustainability, 2012)

Muscular strength and markers of insulin resistance in European adolescents: the HELENA Study - D. Jiménez-Pavón; F. B. Ortega; J. Valtueña; J. Castro-Piñero; S. Gómez-Martínez; M. Zaccaria; F. Gottrand; D. Molnár; M. Sjöström; M. González-Gross; M. J. Castillo; L. A. Moreno; et al. (European Journal of Applied Physiology, 2012)

The second sodium pump: from the function to the gene - Miguel A. Rocafull; Luz E. Thomas; Jesús R. del Castillo (Pflügers Archiv - European Journal of Physiology, 2012)

Diversity of Flavobacterium psychrophilum and the potential use of its phages for protection against bacterial cold water disease in salmonids - D Castillo; G Higuera; M Villa; M Middelboe; I Dalsgaard; L Madsen; R T Espejo (Journal of Fish Diseases, 2012)
Flavobacterium psychrophilum causes rainbow trout fry syndrome (RTFS) and cold water disease (CWD) in salmonid aquaculture. We report characterization of F. psychrophilum strains and their bacteriophages isolated in Chilean salmonid aquaculture. Results suggest that under laboratory conditions phages can decrease mortality of salmonids from infection by their F. psychrophilum host strain. Twelve F. psychrophilum isolates were characterized, with DNA restriction patterns showing low diversity between strains despite their being obtained from different salmonid production sites and from different tissues. We isolated 15 bacteriophages able to infect some of the F. psychrophilum isolates and characterized six of them in detail. DNA genome sizes were close to 50 Kbp and corresponded to the Siphoviridae and Podoviridae families. One isolate, 6H, probably contains lipids as an essential virion component, based on its chloroform sensitivity and low buoyant density in CsCl. Each phage isolate rarely infected F. psychrophilum strains other than the strain used for its enrichment and isolation. Some bacteriophages could decrease mortality from intraperitoneal injection of its host strain when added together with the bacteria in a ratio of 10 plaque‐forming units per colony‐forming unit. While we recognize the artificial laboratory conditions used for these protection assays, this work is the first to demonstrate that phages might be able protect salmonids from RTFS or CWD.

Wholesale replacement of lima bean (Phaseolus lunatus L.) landraces over the last 30 years in northeastern Campeche, Mexico - J. Martínez-Castillo; L. Camacho-Pérez; J. Coello-Coello; R. Andueza-Noh (Genetic Resources and Crop Evolution, 2012)

Inexorable spread: inexorable death? The fate of neo-XY chromosomes of grasshoppers - CLAUDIO J. BIDAU; DARDO A. MARTÍ; ELIO R. CASTILLO (Journal of Genetics, 2011)

Three thousand years of flank and central vent eruptions of the San Salvador volcanic complex (El Salvador) and their effects on El Cambio archeological site: a review based on tephrostratigraphy - D. Ferrés; H. Delgado Granados; W. Hernández; C. Pullinger; H. Chávez; C. R. Castillo Taracena; C. Cañas-Dinarte (Bulletin of Volcanology, 2011)

Teak Plantations: Economic Bonanza or Environmental Disaster? - Justin T. Hallett; Javier Díaz-Calvo; Jaime Villa-Castillo; Michael R. Wagner (Journal of Forestry, 2011)
Teak (Tectona grandis L.f.) is a high-value tropical hardwood with unique wood properties. Teak timber is diminishing in its native range and most teak now comes from intensively managed plantations outside the native range. With increasing demand for high-quality teak wood, plantation area is only expected to increase. There are currently many criticisms and uncertainties expressed in the literature and in public forums regarding the establishment of new teak plantations. The literature indicates issues limiting the potential for teak including wood quality, silvicultural methods, pest problems, and environmental considerations. A field survey of teak plantations along the Pacific Coast of Mexico revealed that silvicultural methods are well known and effective, and most environmental negatives can be mitigated through landscape-level decisionmaking. This article provides information that can assist institutions and investors in deciding whether to consider plantations of high-quality, short-rotation teak in suitable climatic regions.

Microsatellite loci for the blue swimming crab (Callinectes bellicosus) (Crustacea: Portunidae) from the Gulf of California, Mexico - A. Munguia-Vega; J. Torre; A. Castillo-Lopez; T. Pfister; R. Cudney-Bueno (Conservation Genetics Resources, 2010)

Bond-based linear indices of the non-stochastic and stochastic edge-adjacency matrix. 1. Theory and modeling of ChemPhys properties of organic molecules - Yovani Marrero-Ponce; Eugenio R. Martínez-Albelo; Gerardo M. Casañola-Martín; Juan A. Castillo-Garit; Yunaimy Echevería-Díaz; Vicente Romero Zaldivar; Jan Tygat; José E. Rodriguez Borges; Ramón García-Domenech; Francisco Torrens; Facundo Pérez-Giménez (Molecular Diversity, 2010)

Sleep patterns in Spanish adolescents: associations with TV watching and leisure-time physical activity - Francisco B. Ortega; Palma Chillón; Jonatan R. Ruiz; Manuel Delgado; Ulrike Albers; Jesús L. Álvarez-Granda; Ascensión Marcos; Luis A. Moreno; Manuel J. Castillo (European Journal of Applied Physiology, 2010)

Molecular variability among isolates of Mycosphaerella graminicola, the causal agent of septoria tritici blotch, in Argentina - N. Castillo; C. Cordo; M. R. Simón (Phytoparasitica, 2010)

Association of physical activity with muscular strength and fat-free mass in adolescents: the HELENA study - Diego Moliner-Urdiales; Francisco B. Ortega; Germán Vicente-Rodriguez; Juan P. Rey-Lopez; Luis Gracia-Marco; Kurt Widhalm; Michael Sjöström; Luis A. Moreno; Manuel J. Castillo; Jonatan R. Ruiz (European Journal of Applied Physiology, 2010)

Neo-sex chromosome diversity in Neotropical melanopline grasshoppers (Melanoplinae, Acrididae) - Elio R. D. Castillo; Claudio J. Bidau; Dardo A. Martí (Genetica, 2010)

Consilience of genetics and archaeobotany in the entangled history of rice - Dorian Q. Fuller; Yo-Ichiro Sato; Cristina Castillo; Ling Qin; Alison R. Weisskopf; Eleanor J. Kingwell-Banham; Jixiang Song; Sung-Mo Ahn; Jacob van Etten (Archaeological and Anthropological Sciences, 2010)

Climbing time to exhaustion is a determinant of climbing performance in high-level sport climbers - Vanesa España-Romero; Francisco B. Ortega Porcel; Enrique G. Artero; David Jiménez-Pavón; Ángel Gutiérrez Sainz; Manuel J. Castillo Garzón; Jonatan R. Ruiz (European Journal of Applied Physiology, 2009)

Effect of exogenous arginine on sugarcane (Saccharum sp.) somatic embryogenesis, free polyamines and the contents of the soluble proteins and proline - N. Nieves; F. Sagarra; R. González; Y. Lezcano; M. Cid; M. A. Blanco; R. Castillo (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Potential use of seaweeds in the laying hen ration to improve the quality of n-3 fatty acid enriched eggs - S. Carrillo; E. López; M. M. Casas; E. Avila; R. M. Castillo; M. E. Carranco; C. Calvo; F. Pérez-Gil (Journal of Applied Phycology, 2008)

Pitx3 promoter directs Cre-recombinase specifically in a human neuroblastoma cell line - Diana L. Castillo-Carranza; Humberto Rodríguez-Rocha; Roberto Montes-de-Oca-Luna; Julio Sepúlveda-Saavedra; Héctor R. Martínez; Yolanda López-Vidal; Odila Saucedo-Cárdenas (Molecular and Cellular Biochemistry, 2008)

Correlation between the presence of symptoms and the Giardia duodenalis genotype - J. Sahagún; A. Clavel; P. Goñi; C. Seral; M. T. Llorente; F. J. Castillo; S. Capilla; A. Arias; R. Gómez-Lus (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Suitability of weed species prevailing in Spanish vineyards as hosts for root-knot nematodes - P. Castillo; H. F. Rapoport; J. E. Palomares Rius; R. M. Jiménez Díaz (European Journal of Plant Pathology, 2007)

Genetic transformation of Agave salmiana by Agrobacterium tumefaciens and particle bombardment - Silvia Flores-Benítez; Juan F. Jiménez-Bremont; Sergio Rosales-Mendoza; Gerardo R. Argüello-Astorga; Rosalba Castillo-Collazo; Ángel Gabriel Alpuche-Solís (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Carbon emissions from land-use change: an analysis of causal factors in Chiapas, Mexico - M. A. Castillo-Santiago; A. Hellier; R. Tipper; B. H. J. de Jong (Mitigation and Adaptation Strategies for Global Change, 2007)

Early effects of tillage and crop rotation on arbuscular mycorrhizal fungal propagules in an Ultisol - C. G. Castillo; R. Rubio; J. L. Rouanet; F. Borie (Biology and Fertility of Soils, 2006)

Interactions Between Nitrate Assimilation and 2,4-Dinitrophenol Cometabolism in Rhodobacter capsulatus E1F1 - V.M. Luque-Almagro; R. Blasco; L. Paloma Sáez; M. D. Roldán; C. Moreno-Vivián; F. Castillo; M. Martínez-Luque (Current Microbiology, 2006)

Climatic cycles inferred from the aminostratigraphy and aminochronology of Quaternary dunes and palaeosols from the eastern islands of the Canary Archipelago - J. E. Ortiz; T. Torres; Y. Yanes; C. Castillo; J. De La Nuez; M. Ibáñez; M. R. Alonso (Journal of Quaternary Science, 2006)
Aminochronological and aminostratigraphical methods have been used to study the Quaternary aeolian deposits from the islands located east of the Canary Archipelago (Fuerteventura and Lanzarote islands and La Graciosa, Montaña Clara and Alegranza islets). The extent of racemisation/epimerisation of four amino acids (isoleucine, aspartic acid, phenylalanine and glutamic acid) was measured in land snail shells of the genus Theba . The age calculation algorithms of these amino acids have been determined to permit the numerical dating of these deposits. Eight Aminozones, each defining dune/palaeosol‐formation episodes, have been distinguished and dated at 48.6 ± 6.4, 42.5 ± 6.0, 37.8 ± 4.6, 29.4 ± 4.8, 22.4 ± 4.5, 14.9 ± 3.6, 11.0 ± 4.0 and 5.4 ± 1.1 ka BP, the first five of them defining cycles of 5–7 ka. The alternation of palaeosols and aeolian deposits, which are related to abrupt transitions from humid to arid conditions, are the reflection of globally induced changes in North Africa palaeoenvironmental conditions linked to the effect of African palaeomonsoons on the trade winds and the Saharan Air Layer. Probably these aeolian cycles, with a recurrence period of 5–7 ka, are the expression of multiples of the ∼2.4 ka solar‐cycle. Copyright © 2005 John Wiley & Sons, Ltd.

Application of the ‘Climafor’ Approach to Estimate Baseline Carbon Emissions of a Forest Conservation Project in the Selva Lacandona, Chiapas, Mexico - B. H. J. De Jong; A. Hellier; M. A. Castillo-Santiago; R. Tipper (Mitigation and Adaptation Strategies for Global Change, 2005)

Evaluation of an Immunochromatographic Dip-Strip Test for the Detection of Cryptosporidium Oocysts in Stool Specimens - M. Llorente; A. Clavel; M. Varea; S. Olivera; F. Castillo; J. Sahagún; M. Rubio; R. Gómez-Lus (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Cattle as Biomonitors of Soil Arsenic, Copper, and Zinc Concentrations in Galicia (NW Spain) - M. López Alonso; J. L. Benedito; M. Miranda; C. Castillo; J. Hernández; R. F. Shore (Archives of Environmental Contamination and Toxicology, 2002)

Effect of Testosterone Suppression on the Pharmacokinetics of a Potent GnRH Receptor Antagonist - Eugenia A. Iatsimirskaia; Margaret L. Gregory; Kenna L. Anderes; Rosemary Castillo; K. Eric Milgram; David R. Luthin; Ved P. Pathak; Lance C. Christie; Haresh Vazir; Mark B. Anderson; John M. May (Pharmaceutical Research, 2002)

Parasitoid diversity and impact on populations of the diamondback moth Plutella xylostella (L.) on Brassica crops in central México - M. Martínez-Castillo; J.L. Leyva; J. Cibrián-Tovar; R. Bujanos-Muñiz (BioControl, 2002)

Genetic loci associated with field resistance to late blight in offspring of Solanum phureja and S.tuberosum grown under short-day conditions - M. Ghislain; B. Trognitz; Ma. del R. Herrera; J. Solis; G. Casallo; C. Vásquez; O. Hurtado; R. Castillo; L. Portal; M. Orrillo (Theoretical and Applied Genetics, 2001)

Effect of Pre- and Post-Partum Feed Supplementation on the Productive and Reproductive Performance of Grazing Primiparous Brahman Cows - R. Soto; I. Rubio; C.S. Galina; E. Castillo; S. Rojas (Tropical Animal Health and Production, 2001)

Effect of abscisic acid and jasmonic acid on partial desiccation of encapsulated somatic embryos of sugarcane - Nadina Nieves; M. E. Martínez; R. Castillo; María A. Blanco; J. L. González-Olmedo (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Polymorphism of the 5′ terminal region of Citrus tristeza virus (CTV) RNA: Incidence of three sequence types in isolates of different origin and pathogenicity - M. A. Ayllón; C. López; J. Navas-Castillo; S. M. Garnsey; J. Guerri; R. Flores; P. Moreno (Archives of Virology, 2001)

Astrovirus Infection Among Children with Gastroenteritis in the City of Zaragoza, Spain - L. López; F. J. Castillo; M. A. Fernández; A. Clavel; M. C. Rubio; R. Gómez-Lus; B. Cutillas (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Liver injury caused by ebrotidine: a new example of the utility of the postmarketing surveillance - J. R. Castillo; J. Torelló; A. Hernandez (European Journal of Clinical Pharmacology, 2000)

Surface-sediment and epilithic diatom pH calibration sets for remote European mountain lakes (AL:PE Project) and their comparison with the Surface Waters Acidification Programme (SWAP) calibration set - N. G. Cameron; H. J. B. Birks; V. J. Jones; F. Berges; J. Catalan; R. J. Flower; J. Garcia; B. Kawecka; K. A. Koinig; A. Marchetto; P. Sánchez-Castillo; R. Schmidt; et al. (Journal of Paleolimnology, 1999)

Petrology and geochemistry of Camiguin Island, southern Philippines: insights to the source of adakites and other lavas in a complex arc setting - Paterno R. Castillo; Philip E. Janney; Renato U. Solidum (Contributions to Mineralogy and Petrology, 1999)

Synchronous and early activation of planarian Hox genes and the re-specification of body axes during regeneration in Dugesia (G.) tigrina (Turbellaria; Tricladida) - J. R. Bayascas; E. Castillo; A.M. Muñoz-Mármol; J. Baguñà; E. Saló (Hydrobiologia, 1998)

Early history of the Izu–Bonin – Mariana arc system: Evidence from Belau and the Palau Trench - JAMES W. HAWKINS; PATERNO R. CASTILLO (Island Arc, 1998)
Volcanic rocks of the Kyushu–Palau Ridge (KPR) from Deep Sea Drilling Project (DSDP) site 448 and from Belau comprise a low‐to‐medium‐K arc tholeiitic series. Belau rocks include (probable) Mid‐Eocene low‐Ca type‐3 boninite and pre‐Early Oligocene–Early Miocene low‐K arc tholeiitic basalt, basaltic andesite, andesite and dacite. Palau Trench samples include sparsely phyric high‐Mg, ‐Cr and ‐Ni rocks which resemble the Belau boninite and Izu–Bonin – Mariana (IBM) system boninites. The high‐Mg Palau Trench samples also resemble other primitive arc lavas (e.g. arc picrites). Their chemistry suggests an origin involving steep thermal gradients in multiply depleted mantle. Subduction of hot, young lithosphere under a young hot upper plate is postulated to explain this occurrence. The KPR is inferred to be the source of Eocene boninite and arc tholeiitic terranes presently in forearc regions of the IBM system. A model is presented here showing how many IBM boninites may have originated in a small area near Belau. These have migrated eastward by episodic back‐arc opening accompanying eastward migration of arcs and trenches. Oldest known KPR rocks ( ca 47.5 Ma at DSDP site 296), and presumed KPR‐derived exotic terranes of Guam ( ca 43.8 Ma), presage the postulated Eocene ( ca 42–43 Ma) change in Pacific plate motion invoked as the cause of subduction initiation at the KPR. The KPR has been rotated more than 40° clockwise since the Eocene, thus the age mismatch may indicate a different tectonic style, for example transtension or transpression, in earliest KPR history.

Degradation of p -nitrophenol by the phototrophic bacterium Rhodobacter capsulatus - M. D. Roldán; R. Blasco; F. J. Caballero; F. Castillo (Archives of Microbiology, 1997)

Environmental preferences of yellowfin tuna ( Thunnus albacares ) at the northern extent of its range - B. A. Block; J. E. Keen; B. Castillo; H. Dewar; E. V. Freund; D. J. Marcinek; R. W. Brill; C. Farwell (Marine Biology, 1997)